Liquid crystal orientation agent, liquid crystal orientation membrane, liquid crystal cell and compound

The liquid crystal aligning agent with benzophenone structures and crosslinking agents addresses impurity and adhesion issues in high-definition devices, enhancing film stability and reducing production time in PSA type elements.

JP2025009853APending Publication Date: 2025-01-20JSR CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024078857
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2024-05-14
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

High-definition liquid crystal devices face issues with ionic impurities from insulating films eluting into the liquid crystal, leading to deterioration in quality, and require improved impurity resistance, tilt impartability, and mechanical adhesion to prevent substrate peeling, especially in PSA type elements where photopolymerizable compounds can change pretilt angles over time.

Method used

A liquid crystal aligning agent containing specific polymers with benzophenone structures in side chains and crosslinking agents, forming films with enhanced impurity resistance, tilt imparting properties, and adhesion, while minimizing light irradiation time to stabilize pretilt angles.

Benefits of technology

The solution provides liquid crystal alignment films with improved impurity resistance, tilt imparting properties, and mechanical adhesion, stabilizing pretilt angles and reducing production time in PSA type elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009853000031
    Figure 2025009853000031
  • Figure 2025009853000001
    Figure 2025009853000001
  • Figure 2025009853000002
    Figure 2025009853000002
Patent Text Reader

Abstract

To provide a liquid crystal orientation agent capable of obtaining a liquid crystal orientation membrane excellent in impurity resistance, tilt imparting property and sealant adhesion property and further reducing light irradiation time to liquid crystal cells when PSA-type liquid crystal cell is produced.SOLUTION: The liquid crystal orientation agent includes: a first polymer having a structural unit derived from diamine including a group represented by "*-X1-W1", where X1 represents divalent coupling group and W1 represents monovalent group containing benzophenone structure, and having a group represented by "*-X1-W1" as side chain; and a second polymer which is polyamic acid and the like and different from the first polymer. At least one type selected from the group consisting of the first polymer and the second polymer has a structural unit derived from diamine having nitrogen-containing structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal alignment film, a liquid crystal element, and a compound. [Background technology]

[0002] Various driving methods have been developed for liquid crystal elements with different electrode structures and physical properties of liquid crystal molecules, and various liquid crystal elements are known, such as TN type, STN type, VA type, MVA type, in-plane switching type (IPS type), FFS type, and optically compensated bend type (OCB type). These liquid crystal elements have a liquid crystal alignment film for aligning liquid crystal molecules. A liquid crystal alignment film is generally formed on a substrate by applying a liquid crystal alignment agent, which is a polymer component dissolved or dispersed in an organic solvent, to the substrate surface and preferably heating the applied liquid crystal alignment film.

[0003] Known techniques for imparting a pretilt angle to liquid crystal molecules include the rubbing method, in which the surface of a coating film formed from a liquid crystal alignment agent is rubbed in a certain direction with a cloth or the like, and the photoalignment method, in which a photosensitive coating film is irradiated with radiation. Another method proposed is PSA (Polymer Sustained Alignment), in which a photopolymerizable compound is added to the liquid crystal in advance and radiation is irradiated while a voltage is applied to the liquid crystal cell, thereby imparting a pretilt angle to liquid crystal molecules near the liquid crystal alignment film. It is said that the PSA technology can improve the response speed of liquid crystal molecules and also improve the transmittance.

[0004] In recent years, with the demand for higher definition and versatility of liquid crystal elements, further improvements in the electrical properties and display quality of liquid crystal elements are required, and various liquid crystal alignment agents have been proposed to achieve this (see, for example, Patent Document 1). Patent Document 1 discloses that a radical generating structure that generates radicals upon light absorption is introduced into a polymer component that constitutes a liquid crystal alignment film, thereby improving the response speed of liquid crystal in a PSA type liquid crystal display element. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 033921 Summary of the Invention [Problem to be solved by the invention]

[0006] As liquid crystal elements become more highly precise, the quality requirements become more stringent. For example, high-resolution liquid crystal panels such as 4K and 8K are often provided with an insulating film. On the other hand, in liquid crystal panels provided with an insulating film, ionic impurities from the insulating film may dissolve into the liquid crystal through the liquid crystal alignment film. If ionic impurities dissolve into the liquid crystal, there is a concern that the quality of the liquid crystal element may deteriorate, such as by lowering the voltage retention rate or increasing the amount of accumulated charge. Therefore, the liquid crystal alignment film is required to have a property (hereinafter also referred to as "impurity resistance") that suppresses the intrusion of impurities generated in the element into the liquid crystal and is unlikely to cause a deterioration in the quality of the liquid crystal element due to impurities. In addition, considering the application to the manufacture of PSA type liquid crystal elements, it is desirable that the desired pretilt angle can be imparted with as little irradiation as possible when irradiating light to the liquid crystal cell (hereinafter also referred to as "tilt imparting property").

[0007] High-definition liquid crystal elements require not only further improvements in impurity resistance and tilt imparting properties, but also liquid crystal alignment films with excellent mechanical properties and adhesion to substrates. For example, in mobile applications such as smartphones and tablet PCs, as well as large TVs and PC monitors, narrowing of the frame is being attempted from the viewpoint of design and miniaturization of display devices. One method for narrowing the frame is to form a liquid crystal alignment film on the entire substrate surface, and then apply a sealant onto the liquid crystal alignment film to bond the substrates together. On the other hand, when a sealant is placed on the liquid crystal alignment film, force is likely to be applied to the liquid crystal alignment film part where the sealant is placed. Therefore, if the mechanical strength of the liquid crystal alignment film or adhesion to the substrate is insufficient, the adhesion between the substrates (hereinafter also referred to as "sealant adhesion") will decrease, and there is a concern that the substrates will be easily peeled off due to the action of external forces, etc.

[0008] In a PSA type liquid crystal element, if the photopolymerizable compound remains in the liquid crystal layer, there is a concern that the pretilt angle of the liquid crystal will change over time due to the polymerization reaction of the remaining photopolymerizable compound. Therefore, in the manufacturing process of a PSA type liquid crystal element, after performing light irradiation for imparting a pretilt angle to the liquid crystal (hereinafter also referred to as "first irradiation"), the liquid crystal cell may be irradiated with light of an intensity equal to or weaker than that of the first irradiation for a long period of time (for example, about 100 minutes) without applying a voltage to the liquid crystal cell in order to consume the photopolymerizable compound in the liquid crystal (hereinafter also referred to as "second irradiation"). It is considered possible to promote the consumption of the photopolymerizable compound in the liquid crystal layer by extending the light irradiation time by this second irradiation, but there is a concern that the damage to the liquid crystal cell will increase due to the extension of the second irradiation. From the viewpoint of minimizing the damage to the liquid crystal cell by the second irradiation, it is desirable to consume the photopolymerizable compound in the liquid crystal by the second irradiation while shortening the light irradiation time by the second irradiation as much as possible, thereby suppressing the change in the pretilt angle over time.

[0009] The present invention has been made in consideration of the above problems, and has as its main object to provide a liquid crystal alignment agent which can obtain a liquid crystal alignment film having excellent impurity resistance, tilt imparting property, and sealant adhesion property, and can also shorten the light irradiation time for a liquid crystal cell during the manufacture of a PSA type liquid crystal element. [Means for solving the problem]

[0010] According to the present invention, there are provided the following liquid crystal aligning agent, liquid crystal alignment film, liquid crystal element and compound.

[0011] [1] "*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and includes a structural unit derived from a diamine having "*-X 1 -W 1" at its side chain, and a second polymer which is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane, and addition polymer, and which is substantially free of a structural unit having a benzophenone structure, wherein the at least one selected from the group consisting of the first polymer and the second polymer has a secondary amino group, a tertiary amino group, 1 -NR 1 -* 2 and nitrogen-containing heterocyclic structures (wherein R 1 is a monovalent leaving group. 1 " and "* 2 " represents a bond to a carbon atom other than the carbon in the (thio)carbonyl group. A liquid crystal aligning agent comprising a structural unit derived from a diamine having the formula:

[0012] [2] "*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and includes a structural unit derived from a diamine having "*-X 1 -W 1 A liquid crystal aligning agent comprising: a polymer having a group represented by the formula:

[0013] [3] A liquid crystal alignment film formed using the liquid crystal alignment agent according to [1] or [2] above. [4] A liquid crystal element comprising the liquid crystal alignment film according to [3] above. [5] A compound represented by the following formula (CA-1-1): [ka] (In formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms. 1 is an oxygen atom or -NR 9 -It is. 9 R is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 5 and R6 are each independently a monovalent substituent. r1 is an integer of 0 to 4. r2 is an integer of 0 to 5. Effect of the Invention

[0014] According to the liquid crystal aligning agent of the present invention, a liquid crystal alignment film having excellent impurity resistance, tilt imparting property, and sealant adhesion can be obtained. In addition, according to the liquid crystal aligning agent of the present invention, the time of light irradiation to a liquid crystal cell during the production of a PSA type liquid crystal element can be shortened. [Brief description of the drawings]

[0015] [Figure 1] 1H-NMR spectrum of compound (DA-3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The liquid crystal alignment agent of the present disclosure includes a structural unit derived from a specific diamine having a benzophenone structure, and contains a polymer having a benzophenone structure in a side chain. Specific embodiments of the liquid crystal alignment agent of the present disclosure include the following first liquid crystal alignment agent and second liquid crystal alignment agent.

[0017] First liquid crystal alignment agent: "*-X 1 -W 1 " and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 " at its side chain, and a second polymer which is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane, and addition polymer, and which is substantially free of structural units having a benzophenone structure. At least one selected from the group consisting of the first polymer and the second polymer has a secondary amino group, a tertiary amino group, * 1 -NR 1 -* 2 and a nitrogen-containing heterocyclic structure (hereinafter also referred to as "nitrogen-containing structure FN").1 -W 1 In the group represented by ", X 1 is a divalent linking group, W 1 is a monovalent group having a benzophenone structure, and "*" represents a bond (hereinafter the same). 1 -NR 1 -* 2 In the group represented by the formula 1 is a monovalent leaving group, and "* 1 " and "* 2 " represents a bond to a carbon atom other than the carbon in the (thio)carbonyl group.

[0018] Second liquid crystal alignment agent: "*-X 1 -W 1 " and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 " at its side chain, and a crosslinking agent. Hereinafter, a first liquid crystal aligning agent which is a first embodiment of the liquid crystal aligning agent of the present disclosure and a second liquid crystal aligning agent which is a second embodiment of the liquid crystal aligning agent of the present disclosure will be described.

[0019] Here, in this specification, the term "hydrocarbon group" includes chain-shaped hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-shaped hydrocarbon group" means a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, the chain-shaped hydrocarbon group may be saturated or unsaturated. The term "alicyclic hydrocarbon group" means a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, the alicyclic hydrocarbon group does not necessarily have to be composed only of an alicyclic hydrocarbon structure, and also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" means a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, the aromatic hydrocarbon group does not necessarily have to be composed only of an aromatic ring structure, and may include a chain structure or an alicyclic hydrocarbon structure as a part of it. The term "aromatic ring" includes aromatic hydrocarbon rings and aromatic heterocycles. The term "organic group" means an atomic group obtained by removing any hydrogen atom from a compound containing carbon (i.e., an organic compound).

[0020] The "main chain" of a polymer refers to the "trunk" portion of the polymer that is the longest chain of atoms. It is permissible for this "trunk" portion to contain a ring structure. For example, "having a specific structure in the main chain" means that the specific structure constitutes a part of the main chain. A "side chain" refers to a portion that branches off from the "trunk" of a polymer. "(Thio)carbonyl" is intended to include carbonyl and thiocarbonyl.

[0021] <First liquid crystal alignment agent> The first liquid crystal alignment agent contains the above-mentioned first polymer and second polymer. Unless otherwise specified, each component contained in the liquid crystal alignment agent may be used alone or in combination of two or more.

[0022] The first polymer is represented by "*-X 1 -W 1 The type of the main skeleton is not particularly limited as long as a polymer containing a structural unit derived from a diamine having a group represented by "*-X" can be obtained. The first polymer is preferably a condensation polymer obtained by using a monomer containing a diamine compound, and examples thereof include polyamic acid, polyamic acid ester, polyimide, polyamide, and polyamideimide. From the viewpoint of obtaining a liquid crystal element having excellent liquid crystal alignment properties and electrical properties, and from the viewpoint of obtaining a polymer having a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 From the viewpoint of ease of introduction of a structural unit derived from a diamine having a group represented by the formula: ", the first polymer is preferably at least one selected from the group consisting of polyamic acid and polyimide, and more preferably polyamic acid.

[0023] The second polymer is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane, and addition polymer. By using the above-mentioned polymer as the second polymer, uneven distribution of the first polymer in the film can be promoted, and thus tilt imparting ability can be improved. When the first polymer is polyimide, the second polymer is preferably at least one selected from the group consisting of polyamic acid, polyorganosiloxane, and addition polymer, in terms of enhancing the effect of improving the tilt imparting ability and seal adhesion of the liquid crystal alignment film, and more preferably polyamic acid, in terms of enhancing the effect of reducing residual DC. The second polymer is substantially free of structural units having a benzophenone structure, and in this respect is different from the first polymer.

[0024] In addition, it is acceptable for the second polymer to contain a small amount of structural units having a benzophenone structure within a range that does not impair the effects of the present invention. Specifically, the content ratio of structural units having a benzophenone structure in the second polymer is preferably less than 0.5 mol%, more preferably less than 0.1 mol%, and even more preferably 0 mol%, based on the total amount of structural units derived from the monomers constituting the second polymer.

[0025] Preferred embodiments of the combination of the first polymer and the second polymer contained in the liquid crystal aligning agent include the following embodiments [1A] to [4A]. [Aspect 1A] An aspect in which the first polymer and the second polymer are polyamic acids. [Aspect 2A] An aspect in which the first polymer is a polyamic acid, and the second polymer is a polyamic acid and a polyorganosiloxane or an addition polymer. [Aspect 3A] An aspect in which the first polymer is a polyamic acid, and the second polymer is at least one selected from the group consisting of polyimide, polyorganosiloxane, and addition polymer. [Aspect 4A] An aspect in which the first polymer is a polyimide, and the second polymer is at least one selected from the group consisting of polyamic acid, polyorganosiloxane, and addition polymers.

[0026] From the viewpoint of promoting uneven distribution of the first polymer in the film and further enhancing the tilt-imparting ability, among the above, Aspect 1A, Aspect 2A, or Aspect 3A is preferred, and Aspect 1A is more preferred in that a liquid crystal alignment film excellent in tilt-imparting ability and adhesion to a sealant can be obtained.

[0027] In the first liquid crystal alignment agent, the first polymer is "*-X 1 -W 1 " In addition, one or both of the first polymer and the second polymer contain a structural unit derived from a diamine having a nitrogen-containing structure FN.

[0028] When the first polymer contains a structural unit derived from a diamine having a nitrogen-containing structure FN, the first polymer is represented by the formula "*-X 1 -W 1 " and a nitrogen-containing structure FN, and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 " may contain a structural unit derived from a diamine that does not have a group represented by "*-X 1 -W 1 From the viewpoint of ease of synthesis of the monomer, when the first polymer contains a structural unit derived from a diamine having a nitrogen-containing structure FN, the first polymer may contain a structural unit represented by "*-X 1 -W 1 " and a nitrogen-containing structure FN, and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 It is preferable that the diamine contains a structural unit derived from a diamine that does not have a group represented by the formula (I).

[0029] When the second polymer is a polyorganosiloxane or an addition polymer, the first polymer contains a structural unit derived from a diamine having a nitrogen-containing structure FN.

[0030] One or both of the first polymer and the second polymer may be represented by "*-X1 -W 1 " and a functional group different from the nitrogen-containing structure FN. In order to further enhance the tilt-imparting ability of the liquid crystal alignment film, it is preferable that one or both of the first polymer and the second polymer contain a structural unit having a vertical alignment group.

[0031] The structural unit having a vertical alignment group may be contained in the first polymer, may be contained in the second polymer, or may be contained in both the first polymer and the second polymer. In addition, when the structural unit having a vertical alignment group is a structural unit derived from a diamine, the diamine that gives the structural unit having a vertical alignment group is a diamine represented by the formula "*-X 1 -W 1 " and the nitrogen-containing structure FN, and may be a diamine having neither the group represented by "*-X 1 -W 1 " and a nitrogen-containing structure FN.

[0032] For example, when the first polymer contains a structural unit derived from a diamine having a vertical alignment group, the first polymer is represented by the formula "*-X 1 -W 1 " and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 " may contain a structural unit derived from a diamine that does not have a group represented by "*-X 1 -W 1 The first polymer may contain a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 From the viewpoint of ease of synthesis of the monomer and ease of adjusting the content of each functional group in the polymer, when the first polymer contains a structural unit derived from a diamine having a vertical alignment group, the first polymer may contain a structural unit represented by "*-X 1 -W 1" and a structural unit derived from a diamine having a group represented by "*-X 1 -W 1 It is preferable that the diamine contains a structural unit derived from a diamine that does not have a group represented by the formula (I).

[0033] From the viewpoint of increasing the tilt-imparting ability of the liquid crystal alignment film, it is preferable that at least the first polymer contains a structural unit having a vertical alignment group, and from the viewpoint of ease of synthesis, it is more preferable that the structural unit having a vertical alignment group in the first polymer is a structural unit derived from a diamine having a vertical alignment group.

[0034] One or both of the first polymer and the second polymer may further comprise "*-X 1 -W 1 " and the functional group represented by the nitrogen-containing structure FN, *-NR 2 -CO- or *-CO-NR 2 - is bonded to the partial structure (where R 2 is a hydrogen atom or a monovalent organic group, and "*" represents a bond to the aromatic ring.) may contain a structural unit derived from a diamine having *-NR 2 -CO- or *-CO-NR 2 By introducing a partial structure having - bonded thereto into the polymer component, the effect of suppressing accumulation of electric charges in a liquid crystal device can be further enhanced.

[0035] Aromatic ring: *-NR 2 -CO- or *-CO-NR 2 The partial structure having - bonded thereto may be introduced into the main chain or into the side chain of one or both of the first polymer and the second polymer. 2 -CO- or *-CO-NR 2 A part of the partial structure to which - is bonded may be introduced into the main chain, and the remaining part may be introduced into the side chain. 2 -CO- or *-CO-NR 2 The diamine that gives a structural unit having a partial structure with - is "*-X 1 -W 1", a diamine having neither a nitrogen-containing structure FN nor a vertical alignment group, 1 -W 1 ", a nitrogen-containing structure FN, or a vertical alignment group.

[0036] For example, the first polymer may have an aromatic ring having a -NR 2 -CO- or *-CO-NR 2 When the first polymer contains a structural unit derived from a diamine having a partial structure to which *-X 1 -W 1 " and a structural unit derived from a diamine having a group represented by *-NR 2 -CO- or *-CO-NR 2 - is bonded to a partial structure, and "*-X 1 -W 1 " may contain a structural unit derived from a diamine that does not have a group represented by "*-X 1 -W 1 " and an aromatic ring having -NR 2 -CO- or *-CO-NR 2 The first polymer may contain a structural unit derived from a diamine having a partial structure to which - is bonded.

[0037] In addition, when the second polymer is a polyorganosiloxane or an addition polymer, the first polymer has an aromatic ring having *-NR 2 -CO- or *-CO-NR 2 It is preferable that the diamine contains a structural unit derived from a diamine having a partial structure to which - is bonded.

[0038] Next, the "*-X 1 -W 1 ", a structural unit derived from a diamine having a nitrogen-containing structure FN, a structural unit having a vertical alignment group, and a structural unit having a *-NR 2 -CO- or *-CO-NR 2The structural units derived from diamines having a partial structure with - are described in detail below. For convenience, the structural units are referred to as "*-X 1 -W 1 " is a "structural unit (UA)", a structural unit derived from a diamine having a nitrogen-containing structure FN is a "structural unit (UB)", a structural unit having a vertical alignment group is a "structural unit (UC)", and a structural unit having an aromatic ring with *-NR 2 -CO- or *-CO-NR 2 A structural unit derived from a diamine having a partial structure with - bonded thereto is also referred to as a "structural unit (UD)". However, each structural unit may have multiple types of functional groups. For example, a structural unit (UA) is "*-X 1 -W 1 " may have a nitrogen-containing structure FN together with the group represented by "*-X 1 -W 1 A structural unit having a group represented by " and a nitrogen-containing structure FN is both a structural unit (UA) and a structural unit (UB). 1 -W 1 A structural unit having a group represented by the formula "" and a vertically aligning group is both a structural unit (UA) and a structural unit (UC).

[0039] About structural units (UA) The structural unit (UA) of the first polymer is “*-X 1 -W 1 " (wherein X 1 is a divalent linking group, W 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) is a structural unit derived from a diamine having X. 1 The divalent linking group represented by the formula: -O-, -CO-O-* 1 , -O-CO-* 1 , -NR 3 -CO-* 1 , -CO-NR 3 -* 1 , -Y 1 -R 7 -Y 2 -* 1 , -R 8 -Z1 -* 1 etc.

[0040] Where X 1 In the divalent linking group represented by the formula: 3 R is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 7 R is a divalent chain hydrocarbon group having 1 to 20 carbon atoms, a divalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms. 7 Of these, Y is preferably a divalent chain hydrocarbon group having 1 to 20 carbon atoms, and more preferably an alkanediyl group having 1 to 10 carbon atoms. 1 and Y 2 are, independently of each other, -O-, -CO-O-* 2 , -O-CO-* 2 , -NR 4 -CO-* 2 or -CO-NR 4 -* 2 R 4 R is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. 8 R is an alkanediyl group having 1 to 10 carbon atoms. 8 Among these, an alkanediyl group having 1 to 3 carbon atoms is preferable. 1 is an oxygen atom or -NR 9 -It is. 9 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 1 " is W 1 It represents a bond with "*". 2 " represents a bond to an alkanediyl group. In addition, "*-X" in the structural unit (UA) 1 -W 1 The group represented by the formula: is disposed on a side chain of the first polymer.

[0041] R 9The monovalent thermally detachable group represented by is an organic group that is detached by heat. Examples of the thermally detachable group include a carbamate-based detachable group, an amide-based detachable group, an imide-based detachable group, and a sulfonamide-based detachable group. Among these, a carbamate-based detachable group is preferred because of its high thermal detachability. Specific examples of the carbamate-based detachable group include a tert-butoxycarbonyl group, a benzyloxycarbonyl group, a 1,1-dimethyl-2-haloethyloxycarbonyl group, an allyloxycarbonyl group, a 2-(trimethylsilyl)ethoxycarbonyl group, and a 9-fluorenylmethyloxycarbonyl group (F-moc group). Among these, a tert-butoxycarbonyl group (Boc group) is particularly preferred because of its excellent thermal detachability and the reduced amount of the deprotected portion remaining in the film.

[0042] The diamine that provides the structural unit (UA) (hereinafter also referred to as the "first diamine") is preferably an aromatic diamine. The two primary amino groups in the first diamine are preferably bonded to the same aromatic ring, and more preferably bonded to the same benzene ring (i.e., have a diaminophenyl group). When the first diamine has a diaminophenyl group, the bonding position of one amino group bonded to the benzene ring is not particularly limited, and the bonding position of the other group ("*-X 1 -W 1 "), among which the 2,4-positions or 3,5-positions are preferred.

[0043] The benzophenone structure has a structure in which two benzene rings are linked by a carbonyl group. In the benzophenone structure in the first diamine, a substituent may be bonded to the benzene ring. Examples of the substituent include a halogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a vertical alignment group, and a group having a nitrogen-containing structure FN.

[0044] A preferred specific example of the first diamine is a compound represented by the following formula (CA-1). [ka] (In formula (CA-1), X 1 is a divalent linking group. 2 is a single bond or "*-X 1 -W 1 " is a divalent group having a partial structure represented by R 5 and R 6 are each independently a monovalent substituent. r1 is an integer of 0 to 4. r2 is an integer of 0 to 5.

[0045] In the above formula (CA-1), R 5 Examples of the monovalent substituent represented by R include a halogen atom, an alkyl group, an alkoxy group, and a hydroxyl group. 6 Examples of the monovalent substituent represented by the formula (I) include a halogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a vertically aligning group, and a group having a nitrogen-containing structure FN. X 2 is preferably a single bond from the viewpoint of ease of synthesis of the monomer. X 1 Specific examples of the divalent linking group represented by the following formula (I) and the bonding positions of the two primary amino groups are as described above.

[0046] More specific examples of the first diamine include compounds represented by the following formulae (C1-1) to (C1-24), in which "Boc" represents a tert-butoxycarbonyl group (hereinafter the same). [ka] [ka]

[0047] The content of the structural unit (UA) in the first polymer is preferably 1 mol% or more, more preferably 2 mol% or more, and even more preferably 5 mol% or more, based on the total amount of the structural units derived from the monomers constituting the first polymer. The content of the structural unit (UA) is preferably 50 mol% or less, more preferably 30 mol% or less, based on the total amount of the structural units derived from the monomers constituting the first polymer. When the content of the structural unit (UA) in the first polymer is within the above range, better tilt-imparting properties can be ensured, and a liquid crystal element in which the change in pretilt angle over time is suppressed can be obtained while shortening the irradiation time of the second irradiation during the production of a PSA type liquid crystal element.

[0048] The compounds represented by the above formula (C1-14) or (C1-15) and the compounds represented by the above formulas (C1-20) to (C1-22) are each represented by the formula "*-X 1 -W 1 " and a nitrogen-containing structure FN. 1 -W 1 The content of the structural unit derived from the diamine having the group represented by "*-X 1 -W 1 " and a vertical alignment group. 1 -W 1 The content of the structural unit derived from the diamine having a group represented by "*-X" and a vertical alignment group is described in the same manner as in the structural unit (UA). Similarly, the compounds represented by the above formulae (C1-2), (C1-5), (C1-7), (C1-8), (C1-9) and (C1-12) are each represented by "*-X 1 -W 1 " and an aromatic ring having -NR 2 -CO- or *-CO-NR 2 It is a diamine having a partial structure in which "*-X 1 -W 1 " and an aromatic ring having -NR 2 -CO- or *-CO-NR 2With regard to the content ratio of the structural unit derived from the diamine having a partial structure to which - is bonded, the explanation of the structural unit (UA) is applied.

[0049] A compound represented by the formula (CA-1-1) According to the present invention, there is provided a compound represented by the following formula (CA-1-1): The compound represented by the following formula (CA-1-1) is suitable as a monomer of a polymer component to be contained in a liquid crystal alignment agent that can obtain a liquid crystal alignment film having excellent impurity resistance, tilt imparting property, and sealant adhesion, and can shorten the light irradiation time for a liquid crystal cell during the manufacture of a PSA type liquid crystal element. [ka] (In formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms. 1 is an oxygen atom or -NR 9 -It is. 9 R is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 5 and R 6 are each independently a monovalent substituent. r1 is an integer of 0 to 4. r2 is an integer of 0 to 5.

[0050] In the above formula (CA-1-1), R 8 , R 5 , R 6 and R 9 Specific examples are as described above. Specific examples of the compound represented by formula (CA-1-1) above include the compounds represented by formulas (C1-3), (C1-4), (C1-14), and (C1-16) to (C1-24) above.

[0051] The compound represented by the above formula (CA-1-1) can be synthesized by appropriately combining standard methods in organic chemistry. One example of the synthesis method is to synthesize a dinitro intermediate having a nitro group instead of the primary amino group in the above formula (CA-1-1), and then animate the nitro group of the obtained dinitro intermediate using a suitable reduction system.

[0052] The method of synthesizing the dinitro body can be appropriately selected according to the target compound. For example, a method of reacting a hydroxyl group-containing compound having a benzophenone structure with a halogenated dinitro compound, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; a method of reacting a hydroxyl group-containing compound having a benzophenone structure with a dinitro compound containing a tosyl group, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; a method of condensing an acid halide having a benzophenone structure with a dinitro compound containing an amino group, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst; a method of condensing a carboxylic acid having a benzophenone structure with a dinitro compound containing an amino group, preferably in an organic solvent, in the presence of a base and, if necessary, a catalyst, and the like can be mentioned.

[0053] The reduction reaction of the dinitro intermediate can be preferably carried out in an organic solvent using a catalyst such as palladium carbon, platinum oxide, zinc, iron, tin, nickel, platinum carbon, osmium carbon, etc. Examples of the organic solvent used here include ethyl acetate, toluene, tetrahydrofuran, alcohols, etc. Two or more of these organic solvents may be mixed and used. However, the synthesis method of the compound represented by the above formula (CA-1-1) is not limited to the above method.

[0054] About structural units (UB) The structural unit (UB) is a secondary amino group, a tertiary amino group, * 1 -NR 1 -* 2 and a nitrogen-containing heterocyclic structure, wherein R is a structural unit derived from a diamine having at least one nitrogen-containing structure FN selected from the group consisting of 1 is a monovalent leaving group. 1 " and "* 2" represents a bond to a carbon atom other than the carbon in the (thio)carbonyl group. Since the liquid crystal alignment agent of the present disclosure contains a polymer having the structural unit (UB), in a liquid crystal element having a liquid crystal alignment film formed from the first liquid crystal alignment agent, impurities originating from the insulating film and the like are adsorbed by the liquid crystal alignment film and kept within the film, thereby enhancing the effect of suppressing the intrusion of impurities into the liquid crystal layer, and it is considered that this makes it possible to suppress a decrease in the voltage holding ratio caused by the generation of impurities.

[0055] The diamine that provides the structural unit (UB) (hereinafter also referred to as the "second diamine") is 1 -NR 1 -* 2 If R 1 The leaving group represented by the formula (I) is preferably a thermally detachable group which is detached by heat. 9 The explanation of the thermally detachable group represented by the following formula (1) is applied.

[0056] * 1 -NR 1 -* 2 The two bonds of the group represented by the formula (I) are preferably bonded to an alkanediyl group, a substituted or unsubstituted divalent alicyclic group, or a substituted or unsubstituted divalent aromatic ring group. Among these, an alkanediyl group is preferred, and a straight-chain alkanediyl group is more preferred, in that it can enhance the effect of improving the adhesion of the seal material.

[0057] (Nitrogen-containing heterocyclic structure) The nitrogen-containing heterocycle in the nitrogen-containing heterocyclic structure may be an aromatic heterocycle or an aliphatic heterocycle. The nitrogen-containing heterocycle may be a single ring or a condensed ring. Specific examples of these include nitrogen-containing aromatic heterocycles such as pyrrole ring, imidazole ring, pyrazole ring, triazole ring, pyridine ring, pyrimidine ring, pyridazine ring, quinoline ring, benzimidazole ring, carbazole ring, and pyrazine ring. Examples of nitrogen-containing aliphatic heterocycles include piperidine ring, piperazine ring, morpholine ring, and hexamethyleneimine ring.

[0058] The nitrogen-containing heterocycle of the second diamine is preferably at least one selected from the group consisting of pyridine ring, pyrimidine ring, pyrazine ring, piperidine ring, piperazine ring, quinoline ring, imidazole ring and benzimidazole ring. The nitrogen-containing heterocycle is preferably a pyridine ring, piperazine ring or imidazole ring from the viewpoint of strong basicity, and more preferably a pyridine ring from the viewpoint of polymer solubility. The nitrogen-containing heterocycle of the second diamine may have a substituent bonded thereto. Examples of the substituent include an alkyl group having 1 to 3 carbon atoms.

[0059] When the structural unit (UB) has a nitrogen-containing heterocycle, the polymer containing the structural unit (UB) may have the nitrogen-containing heterocycle structure in the main chain or in the side chain. The polymer containing the structural unit (UB) may have the nitrogen-containing heterocycle in both the main chain and the side chain. In terms of being able to further improve the effect of improving impurity resistance, it is particularly preferable that the polymer containing the structural unit (UB) has the nitrogen-containing heterocycle in the side chain.

[0060] Specific examples of the nitrogen-containing heterocyclic structure include partial structures represented by the following formulas (2a-1) to (2a-12). [ka] (In formulas (2a-1) to (2a-12), "*" represents a bond.)

[0061] From the viewpoint of further improving the impurity resistance of the liquid crystal element, the diamine (second diamine) that gives the structural unit (UB) preferably has a nitrogen-containing heterocyclic structure among the above, and more preferably has at least one selected from the group consisting of a pyridine ring, a pyrimidine ring, a pyrazine ring, a piperidine ring, a piperazine ring, a quinoline ring, an imidazole ring, and a benzimidazole ring. Among these, it is particularly preferable that the second diamine is a diamine that can introduce a nitrogen-containing heterocyclic structure into the side chain of a polymer.

[0062] Specific examples of the second diamine include the compounds represented by the following formulas (C2-1) to (C-29), the compounds represented by the above formulas (C1-14) or (C1-15), and the compounds represented by the formulas (C1-20) to (C1-22). [ka] [ka]

[0063] The structural unit (UB) may be contained in the first polymer or in the second polymer. In addition, both the first polymer and the second polymer may have the structural unit (UB). From the viewpoint of suppressing accumulation of electric charges caused by impurities in the liquid crystal element when the liquid crystal element is driven and obtaining a liquid crystal element in which DC afterimages are unlikely to occur, it is preferable that the first polymer contains the structural unit (UA) and the structural unit (UB). In this case, the second polymer may or may not contain the structural unit (UB). When the first polymer contains the structural unit (UA) and the structural unit (UB), the first polymer has a nitrogen-containing structure FN and is a compound represented by the formula "*-X 1 -W 1 It is preferable that the structural unit (UB) is contained in addition to the structural unit (UA) by containing a structural unit derived from a diamine that does not have a group represented by the formula (1).

[0064] When the first polymer contains the structural unit (UB), the content of the structural unit (UB) is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total amount of the structural units derived from the monomers constituting the first polymer. The content of the structural unit (UB) is preferably 70 mol% or less, more preferably 50 mol% or less, based on the total amount of the structural units derived from the monomers constituting the first polymer. By setting the content of the structural unit (UB) in the first polymer within the above range, it is preferable to form a liquid crystal alignment film that exhibits better impurity resistance.

[0065] The content of the structural unit (UB) in the second polymer is preferably 40 mol % or less, and more preferably 20 mol % or less, based on the total amount of structural units derived from monomers constituting the second polymer.

[0066] About structural units (UC) The structural unit (UC) is introduced into the polymer component for the purpose of imparting a pretilt angle to an organic film formed using the liquid crystal alignment agent. By incorporating a polymer having a vertical alignment group in the side chain into the liquid crystal alignment agent of the present disclosure, the tilt imparting ability of the liquid crystal alignment film can be further improved.

[0067] The vertical alignment group is a group having a function of imparting a pretilt angle to the liquid crystal alignment film. Examples of the vertical alignment group include an alkyl group having 4 to 30 carbon atoms, an alkoxy group having 4 to 30 carbon atoms, a fluoroalkyl group having 4 to 30 carbon atoms, a fluoroalkoxy group having 4 to 30 carbon atoms, a group having a structure in which a chain structure having 1 to 20 carbon atoms is bonded to an alicyclic or aromatic ring, a group having a structure in which two or more rings are bonded directly or via a divalent linking group, and a group having 17 to 51 carbon atoms and a steroid skeleton.

[0068] A preferred specific example of the vertical alignment group is a group represented by the following formula (3). *-R 31 -R 32 -R 33 -R 34 …(3) (In formula (3), R 31 and R 33 are each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group; R 32 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 37 -B 31 -R 38 -(However, R 37 and R 38 are each independently a substituted or unsubstituted phenylene group or cycloalkylene group; B 31 is a single bond, -O-, -COO-*4 , -OCO-* 4 , -OCH2-* 4 , -CH2O-* 4 or an alkanediyl group having 1 to 3 carbon atoms. 4 " is R 38 It represents a bond with . 34 is a hydrogen atom, a fluorine atom, CH3COO-* 5 ("* 5 " is R 33 represents a bond to the alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a fluoroalkoxy group having 1 to 20 carbon atoms, or a group having a steroid skeleton and having 17 to 51 carbon atoms. 31 , R 32 and R 33 are all single bonds, or R 31 , R 32 and R 33 When the total number of substituted or unsubstituted phenylene groups and substituted or unsubstituted cycloalkylene groups contained in R is 1, 34 is an alkyl group having 4 to 20 carbon atoms, a fluoroalkyl group having 4 to 20 carbon atoms, an alkoxy group having 4 to 20 carbon atoms, a fluoroalkoxy group having 4 to 20 carbon atoms, or a group having a steroid skeleton and having 17 to 51 carbon atoms. "*" represents a bond.)

[0069] In the above formula (3), R 34 The alkyl group having 1 to 30 carbon atoms, the fluoroalkyl group having 1 to 30 carbon atoms, the alkoxy group having 1 to 30 carbon atoms, or the fluoroalkoxy group having 1 to 30 carbon atoms represented by the following formula (I) is preferably linear. These groups preferably have 2 to 30 carbon atoms, more preferably have 3 to 30 carbon atoms, and further preferably have 4 to 30 carbon atoms. R 31 , R 32 and R 33 When all of are single bonds, R 34 The number of carbon atoms is preferably 6 or more, more preferably 8 or more, and even more preferably 12 or more. R 34Examples of the group having a steroid skeleton and 17 to 51 carbon atoms include a cholestanyl group, a cholesteryl group, and a lanostannyl group.

[0070] From the viewpoint of obtaining a liquid crystal element that exhibits good liquid crystal alignment and is highly reliable, R 31 , R 32 and R 33 has preferably a total of two or more substituted or unsubstituted phenylene groups and / or cycloalkylene groups, and more preferably has a total of 2 to 4 phenylene groups and / or cycloalkylene groups.

[0071] Specific examples of the group represented by the above formula (3) include groups represented by each of the following formulas (3-1) to (3-15), a linear alkyl group having 8 to 30 carbon atoms, a linear alkoxy group having 8 to 30 carbon atoms, and a linear fluoroalkyl group having 8 to 30 carbon atoms. [ka] (In formulas (3-1) to (3-13), R is a fluorine atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a fluoroalkoxy group having 1 to 20 carbon atoms. X 31 is -O-, -COO-, -OCO- or an alkanediyl group having 1 to 3 carbon atoms. "*" represents a bond.)

[0072] When the monomer that gives the structural unit having a vertical alignment group is a diamine, the diamine having a vertical alignment group (hereinafter also referred to as "third diamine") is preferably an aromatic diamine. The two primary amino groups in the third diamine are preferably bonded to the same aromatic ring, more preferably to the same benzene ring. When the third diamine has a diaminophenyl group, the bonding position of one amino group bonded to the benzene ring is not particularly limited. Specifically, the bonding position may be 2,4-position, 2,5-position, or 3,5-position relative to the other group (group having a vertical alignment group). Of these, the 2,4-position or 3,5-position is preferred.

[0073] The vertical alignment group may be directly bonded to the aromatic ring, or may be bonded to the aromatic ring via a divalent linking group. The divalent linking group may be -O-, -CO-, -COO ... 3 , -OCO-* 3 , -NR 35 -, -NR 35 -CO-* 3 , -CO-NR 35 -* 3 an alkanediyl group having 1 to 6 carbon atoms, a divalent group in which a hydrogen atom of an alkanediyl group having 2 to 6 carbon atoms is substituted with a hydroxyl group, -OR 36 -* 3 , or -R 36 -O-* 3 (However, R 35 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, and R 36 is an alkanediyl group having 1 to 3 carbon atoms. 3 " is R 31 It represents a bond with . )

[0074] The structural unit (UC) may be contained in the first polymer or in the second polymer. In addition, both the first polymer and the second polymer may have the structural unit (UC). From the viewpoint of imparting a desired pretilt angle to an organic film formed using a liquid crystal aligning agent with as little light irradiation as possible, it is preferable that the first polymer contains the structural unit (UA) and the structural unit (UC). In this case, the second polymer may or may not contain the structural unit (UC). When the first polymer contains the structural unit (UA) and the structural unit (UC), the first polymer has a vertical alignment group and is a group represented by "*-X 1 -W 1 It is preferable that the structural unit (UC) is contained in addition to the structural unit (UA) by containing a structural unit derived from a diamine that does not have a group represented by the formula (1).

[0075] When the first polymer contains the structural unit (UC), the content of the structural unit (UC) is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total amount of the structural units derived from the monomers constituting the first polymer. The content of the structural unit (UC) is preferably 50 mol% or less, more preferably 30 mol% or less, based on the total amount of the structural units derived from the monomers constituting the first polymer.

[0076] When the second polymer contains the structural unit (UC), the content of the structural unit (UC) is preferably 0.5 mol% or more, more preferably 1 mol% or more, and even more preferably 2 mol% or more, based on the total amount of the structural units derived from the monomers constituting the second polymer. The content of the structural unit (UC) is preferably 30 mol% or less, more preferably 20 mol% or less, based on the total amount of the structural units derived from the monomers constituting the second polymer.

[0077] About structural units (UD) A structural unit (UD) is an aromatic ring and a *-NR bonded to the aromatic ring. 2 -CO- or *-CO-NR 2 -(However, R 2 is a hydrogen atom or a monovalent organic group, and "*" represents a bond to the aromatic ring.) (hereinafter, also referred to as "fourth diamine"). By introducing the structural unit (UD) into the polymer, the aromatic ring is bonded to *-NR 2 -CO- or *-CO-NR 2 A partial structure in which - is bonded is introduced into the polymer. By incorporating a polymer containing a structural unit (UD) having such a partial structure into a liquid crystal alignment agent, the effect of suppressing the accumulation of electric charges in a liquid crystal element can be further enhanced.

[0078] In the fourth diamine, *-NR 2 -CO- or *-CO-NR 2 The aromatic ring to which - is bonded may be an aromatic hydrocarbon ring or an aromatic heterocyclic ring. Among these, a benzene ring, a naphthalene ring, a pyridine ring, or a pyrimidine ring is preferred. 2 -CO- or *-CO-NR2 The aromatic ring to which - is bonded may further have a substituent, such as an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a halogen atom, or a hydroxyl group.

[0079] R 2 Examples of the monovalent organic group represented by the formula (I) include an alkyl group having 1 to 5 carbon atoms and a monovalent leaving group. Specific and preferred examples of the monovalent leaving group are shown in R 1 The same groups as those described in the description of the leaving group represented by R 2 is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 2 -CO- or *-CO-NR 2 - may form part of a urea bond.

[0080] Aromatic ring: *-NR 2 -CO- or *-CO-NR 2 In the case where a part or all of the partial structure having - bonded thereto is introduced into the side chain of the polymer, specific examples of the fourth diamine include compounds represented by the above formulae (C1-2), (C1-5), (C1-7), (C1-8), (C1-9), (C2-11), (C2-12), (C2-15), (C2-17), (C2-19) and (C2-29), and compounds in which the vertical alignment group is *-NR 2 -CO- or *-CO-NR 2 and compounds in which the aryl group is bonded to a diaminophenyl group via an -.

[0081] Aromatic ring: *-NR 2 -CO- or *-CO-NR 2 When a partial structure having - bonded thereto is introduced into the main chain of the polymer, the fourth diamine is preferably an aromatic diamine, and specifically, a compound represented by the following formula (4) is preferred. [ka] (In formula (4), X 41 and X 42are independent of each other *-NR 2 -CO- or *-CO-NR 2 -. "*" represents the bond to the benzene ring. X 43 and X 44 are each independently a single bond or -NR 43 -It is. 43 R is a hydrogen atom or a monovalent organic group. 40 represents a divalent hydrocarbon group or a hydrocarbon group having -O-, -S-, -NR 44 -, -NR 44 -CO- or -NR 44 -CO-NR 45 R is a divalent group containing -. 44 and R 45 are each independently a hydrogen atom or a monovalent organic group. 41 and R 42 are each independently a monovalent substituent. m1 is an integer of 0 to 3. m2 and m3 are each independently an integer of 0 to 4. When m1 is 2 or more, multiple R 40 are the same or different, and multiple X 44 are the same or different, and multiple X 42 are the same or different.)

[0082] In the above formula (4), R 40 The divalent hydrocarbon group represented by the formula (I) is preferably an aliphatic hydrocarbon group, more preferably an alkanediyl group. 40 The divalent hydrocarbon group represented by the following formula (I) preferably has 1 to 20 carbon atoms, and more preferably has 1 to 10 carbon atoms. R 43 , R 44 or R 45 Specific and preferred examples of the monovalent organic group represented by R 2 The monovalent organic group represented by the formula R 43 , R 44 or R 45 are each preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group.

[0083] Aromatic ring: *-NR 2-CO- or *-CO-NR 2 When a partial structure having - bonded thereto is introduced into the main chain of a polymer, specific examples of the fourth diamine include compounds represented by each of the following formulae (C4-1) to (C4-9). [ka]

[0084] When the first polymer contains the structural unit (UD), the content of the structural unit (UD) is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total amount of the structural units derived from the monomers constituting the first polymer. The content of the structural unit (UD) is preferably 75 mol% or less, more preferably 55 mol% or less, and even more preferably 45 mol% or less, based on the total amount of the structural units derived from the monomers constituting the first polymer.

[0085] In addition, when the second polymer contains the structural unit (UD), the content ratio of the structural unit (UD) is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total amount of the structural units derived from the monomers constituting the second polymer. In addition, the content ratio of the structural unit (UD) is preferably 75 mol% or less, more preferably 55 mol% or less, and even more preferably 45 mol% or less, based on the total amount of the structural units derived from the monomers constituting the second polymer.

[0086] The first polymer and the second polymer may contain a structural unit derived from a diamine (hereinafter also referred to as a "fifth diamine") different from the first diamine, the second diamine, the third diamine, and the fourth diamine. Examples of the fifth diamine include an aliphatic diamine (a chain diamine, an alicyclic diamine), an aromatic diamine, and a diaminoorganosiloxane.

[0087] Specific examples of these include chain diamines such as metaxylylenediamine, 1,3-propanediamine, tetramethylenediamine, pentamethylenediamine, and hexamethylenediamine; alicyclic diamines such as 1,4-diaminocyclohexane and 4,4'-methylenebis(cyclohexylamine); Aromatic diamines include p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylether, 4-aminophenyl-4-aminobenzoate, 4,4'-diaminoazobenzene, 3,5-diaminobenzoic acid, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1 ,6-bis(4-aminophenoxy)hexane, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, 1,4-bis-(4-aminophenyl)-piperazine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-( phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline, 4,4'-diaminobenzanilide, 4,4'-diaminostilbene, 1,4-bis(4-aminophenyl)-piperazine, bis[2-(4-aminophenyl)ethyl]hexane diacid, 4,4'-diaminodiphenethyl urea, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, etc.; As the diaminoorganosiloxane, for example, 1,3-bis(3-aminopropyl)-tetramethylsiloxane tetramethyldisiloxane, etc., and also the diamines described in JP-A-2010-97188 can be used.

[0088] In the first polymer, the content of the structural unit structure derived from the fifth diamine is preferably 80 mol % or less, more preferably 70 mol % or less, based on the total amount of the structural units derived from the monomers constituting the first polymer. In the second polymer, the content of the structural unit structure derived from the fifth diamine is preferably 99 mol % or less, more preferably 95 mol % or less, based on the total amount of the structural units derived from the monomers constituting the second polymer.

[0089] When the first polymer and the second polymer are at least one selected from the group consisting of polyamic acid and polyimide, they can be obtained by a method including a step of reacting a tetracarboxylic dianhydride with a diamine (condensation polymerization reaction). The first polymer and the second polymer thus obtained contain structural units derived from the tetracarboxylic dianhydride and structural units derived from the diamine compound.

[0090] Tetracarboxylic acid dianhydride Examples of the tetracarboxylic dianhydride include aliphatic tetracarboxylic dianhydrides and aromatic tetracarboxylic dianhydrides. The aliphatic tetracarboxylic dianhydrides include chain tetracarboxylic dianhydrides and alicyclic tetracarboxylic dianhydrides.

[0091] Specific examples of these include 1,2,3,4-butanetetracarboxylic dianhydride as a chain tetracarboxylic dianhydride; Alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8-tetracarboxybicyclo[3.3.0]octane-2:4,6:8-dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane tetracarboxylic dianhydride, and the like; Examples of aromatic tetracarboxylic dianhydrides include pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, ethylene glycol bisanhydrotrimate, 4,4'-carbonyldiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, etc. Also, examples of tetracarboxylic dianhydrides that can be used include tetracarboxylic dianhydrides described in JP-A-2010-97188.

[0092] When the second polymer is at least one selected from the group consisting of polyamic acid and polyimide, the content ratio of the structural unit derived from aromatic tetracarboxylic dianhydride in the second polymer is preferably 50 mol % or less with respect to the total amount of the structural units derived from tetracarboxylic dianhydride constituting the second polymer. If the content ratio of the structural units derived from aromatic tetracarboxylic dianhydride constituting the second polymer is high, the impurity resistance tends to be easily reduced. In terms of being able to obtain a liquid crystal element with excellent impurity resistance, the content ratio of the structural units derived from aromatic tetracarboxylic dianhydride constituting the second polymer is more preferably 40 mol % or less, even more preferably 30 mol % or less, and even more preferably 20 mol % or less with respect to the total amount of the structural units derived from tetracarboxylic dianhydride constituting the second polymer.

[0093] When the first polymer is at least one selected from the group consisting of polyamic acid and polyimide, the tetracarboxylic dianhydride constituting the first polymer preferably contains an aliphatic tetracarboxylic dianhydride, in that the solubility of the polymer can be increased and a liquid crystal element exhibiting good electrical properties can be obtained. Specifically, the proportion of the structural units derived from the aliphatic tetracarboxylic dianhydride constituting the first polymer is more preferably 50 mol % or more, even more preferably 70 mol % or more, and even more preferably 80 mol % or more, based on the total amount of the structural units derived from the tetracarboxylic dianhydride constituting the first polymer.

[0094] Next, the methods for producing polyamic acid, polyimide, polyorganosiloxane, and addition polymers will be described.

[0095] Synthesis of polyamic acid The polyamic acid can be obtained by reacting the above-mentioned tetracarboxylic dianhydride and diamine compound together with a molecular weight modifier as necessary. The ratio of the tetracarboxylic dianhydride and diamine compound used in the synthesis reaction of the polyamic acid is preferably such that the acid anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents per equivalent of the amino group of the diamine compound. Examples of the molecular weight modifier include acid monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride; monoamine compounds such as aniline, cyclohexylamine, and n-butylamine; and monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate. The ratio of the molecular weight modifier used is preferably 20 parts by mass or less per 100 parts by mass of the total of the tetracarboxylic dianhydride and diamine compound used.

[0096] The synthesis reaction of polyamic acid is preferably carried out in an organic solvent. The reaction temperature is preferably -20°C to 150°C, and the reaction time is preferably 0.1 to 24 hours. Examples of the organic solvent used in the reaction include aprotic polar solvents, phenolic solvents, alcohols, ketones, esters, ethers, halogenated hydrocarbons, and hydrocarbons. Particularly preferred organic solvents include one or more selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphortriamide, m-cresol, xylenol, and halogenated phenols, or a mixture of one or more of these with other organic solvents (e.g., butyl cellosolve, diethylene glycol diethyl ether, etc.). The amount (a) of the organic solvent used is preferably an amount such that the total amount (b) of the tetracarboxylic dianhydride and the diamine is 0.1 to 50 mass% with respect to the total amount (a+b) of the reaction solution.

[0097] In this manner, a reaction solution in which polyamic acid is dissolved is obtained. This reaction solution may be used as it is for the preparation of a liquid crystal aligning agent, or the polyamic acid contained in the reaction solution may be isolated and then used for the preparation of a liquid crystal aligning agent.

[0098] Polyimide synthesis Polyimide can be obtained, for example, by dehydrating and ring-closing polyamic acid to form an imidized polyimide. The imidization rate of polyimide is preferably 20 to 90%, and more preferably 30 to 85%. The imidization rate is the ratio of the number of imide ring structures to the total number of amic acid structures and imide ring structures of the polyimide, expressed as a percentage.

[0099] The dehydration ring closure of the polyamic acid is preferably carried out by dissolving the polyamic acid in an organic solvent, adding a dehydrating agent and a dehydration ring closure catalyst to the solution, and heating as necessary. In this method, the dehydrating agent may be, for example, an acid anhydride such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride. The amount of the dehydrating agent used is preferably 0.01 to 20 moles per mole of the amic acid structure of the polyamic acid. The dehydration ring closure catalyst may be, for example, a tertiary amine such as pyridine, collidine, lutidine, or triethylamine. The amount of the dehydration ring closure catalyst used is preferably 0.01 to 10 moles per mole of the dehydrating agent used.

[0100] Examples of the organic solvent used in the dehydration ring-closing reaction include the organic solvents exemplified as those used in the synthesis of polyamic acid. The reaction temperature in the dehydration ring-closing reaction is preferably 0 to 180°C. The reaction time is preferably 1.0 to 120 hours. The reaction solution containing the polyimide may be used as it is for the preparation of a liquid crystal alignment agent. Alternatively, the polyimide may be isolated from the reaction solution, and the isolated polyimide may be used for the preparation of a liquid crystal alignment agent.

[0101] Synthesis of polyorganosiloxane Polyorganosiloxanes can be obtained, for example, by hydrolysis and condensation of hydrolyzable silane compounds. Examples of hydrolyzable silane compounds include alkoxysilane compounds such as tetramethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and dimethyldiethoxysilane; nitrogen- and sulfur-containing alkoxysilane compounds such as 3-mercaptopropyltriethoxysilane, mercaptomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(3-cyclohexylamino)propyltrimethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropyltrimethoxysilane; Examples of the epoxy group-containing silane compounds include ethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; unsaturated bond-containing alkoxysilane compounds include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltriethoxysilane, and p-styryltrimethoxysilane; and trimethoxysilylpropylsuccinic anhydride. The hydrolyzable silane compounds may be used alone or in combination of two or more of these. The term "(meth)acryloxy" includes "acryloxy" and "methacryloxy".

[0102] The above hydrolysis and condensation reaction can be carried out by reacting one or more of the above silane compounds with water, preferably in the presence of a suitable catalyst and an organic solvent. In the reaction, the proportion of water used is preferably 1 to 30 moles per mole of the silane compounds (total amount). Examples of the catalyst used include acids, alkali metal compounds, organic bases, titanium compounds, zirconium compounds, etc. The amount of the catalyst used varies depending on the type of catalyst, reaction conditions such as temperature, etc., and should be set appropriately, but is preferably 0.01 to 3 moles per the total amount of the silane compounds. Examples of the organic solvent used include hydrocarbons, ketones, esters, ethers, alcohols, etc. Among these, it is preferable to use a water-insoluble or poorly water-soluble organic solvent. The proportion of the organic solvent used is preferably 10 to 10,000 parts by mass per 100 parts by mass of the total silane compounds used in the reaction.

[0103] The above hydrolysis and condensation reaction is preferably carried out by heating, for example, in an oil bath. In this case, the heating temperature is preferably 130°C or less, and the heating time is preferably 0.5 to 12 hours. After the reaction is completed, the organic solvent layer separated from the reaction solution is dried with a desiccant as necessary, and then the solvent is removed to obtain the desired polyorganosiloxane. The method for synthesizing polyorganosiloxane is not limited to the above hydrolysis and condensation reaction, and may be, for example, a method in which a hydrolyzable silane compound is reacted in the presence of oxalic acid and alcohol.

[0104] As the second polymer, a nitrogen-containing structure FN, a vertically aligning group or an aromatic ring having *-NR 2 -CO- or *-CO-NR 2 When using a polyorganosiloxane having a partial structure in which - is bonded, a polyorganosiloxane having an epoxy group on the side chain is obtained by the above polymerization, and then a nitrogen-containing structure FN, a vertical alignment group, or an aromatic ring is bonded to *-NR 2 -CO- or *-CO-NR 2The polyorganosiloxane may be obtained by reacting the epoxy group-containing polyorganosiloxane with a carboxylic acid having a partial structure to which - is bonded. The reaction between the epoxy group-containing polyorganosiloxane and the carboxylic acid can be preferably carried out in the presence of a catalyst (e.g., a tertiary organic amine, a quaternary organic amine, a quaternary ammonium salt, etc.) and an organic solvent. After the reaction is completed, it is preferable to wash the organic solvent layer separated from the reaction solution with water. After washing with water, the organic solvent layer is dried with an appropriate drying agent as necessary, and then the solvent is removed to obtain the target polyorganosiloxane.

[0105] Synthesis of addition polymers The addition polymer can be obtained by polymerizing one or more monomers having a polymerizable carbon-carbon unsaturated bond. Specific examples of the addition polymer include styrene-based polymers, maleimide-based polymers, styrene-maleimide-based polymers, (meth)acrylic polymers, etc.

[0106] As the monomer constituting the addition polymer, any monomer having a polymerizable unsaturated bond can be used, such as a compound having a (meth)acryloyl group, a vinyl group, a vinylphenyl group, a maleimide group, or the like.

[0107] Specific examples of monomers constituting the addition polymer include unsaturated carboxylic acids such as (meth)acrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, and vinylbenzoic acid; unsaturated carboxylic acid esters such as alkyl (meth)acrylates (e.g., methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.), cycloalkyl (meth)acrylates, benzyl (meth)acrylate, trimethoxysilylpropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, and 4-hydroxybutyl glycidyl ether (meth)acrylate; unsaturated polyvalent carboxylic acid anhydrides such as maleic anhydride; and (meth)acrylic compounds such as: Aromatic vinyl compounds such as styrene, methylstyrene, divinylbenzene and 4-(glycidyloxymethyl)styrene; conjugated diene compounds such as 1,3-butadiene and 2-methyl-1,3-butadiene; Examples of the maleimide-based compounds include N-methylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, N-(4-glycidyloxyphenyl)maleimide, N-glycidylmaleimide, 3-maleimide benzoic acid, 3-maleimide propionic acid, 3-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, and methyl 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoate. In addition, a compound having a vertical alignment group can also be used as a monomer constituting the addition polymer.

[0108] The addition polymer can be obtained, for example, by polymerizing the monomers in the presence of a polymerization initiator. The polymerization initiator used is preferably an azo compound such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), or 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). The proportion of the polymerization initiator used is preferably 0.01 to 30 parts by mass relative to 100 parts by mass of the total monomers used in the reaction. The polymerization reaction is preferably carried out in an organic solvent. Examples of the organic solvent used in the reaction include alcohols, ethers, ketones, amides, esters, and hydrocarbon compounds, and diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether acetate, and the like are preferred. The reaction temperature is preferably 30°C to 120°C, and the reaction time is preferably 1 to 36 hours. The amount (a) of the organic solvent used is preferably set so that the total amount (b) of the monomers used in the reaction is 0.1 to 60 mass % based on the total amount (a+b) of the reaction solution.

[0109] From the viewpoint of further improving the tilt imparting property and the seal adhesion of the liquid crystal alignment film, the second polymer preferably has at least one functional group selected from the group consisting of a carboxy group, an epoxy group, and a hydroxy group. Here, as the polymer having a carboxy group, at least one selected from the group consisting of a polyamic acid and a polyimide can be preferably used. In addition, an addition polymer containing a structural unit derived from a monomer having a carboxy group may be used. As the polymer having an epoxy group, at least one selected from the group consisting of a polyorganosiloxane and an addition polymer can be preferably used. As the polymer having a hydroxy group, at least one selected from the group consisting of a polyamic acid, a polyimide, a polyorganosiloxane, and an addition polymer can be preferably used.

[0110] From the viewpoint of further enhancing the effect of improving the tilt imparting property, impurity resistance and seal adhesion of the liquid crystal alignment film, the second polymer preferably contains a structural unit having at least one functional group selected from the group consisting of a carboxy group, an epoxy group and a hydroxy group. In the second polymer, the content ratio of the structural unit having at least one functional group selected from the group consisting of a carboxy group, an epoxy group and a hydroxy group is preferably 1 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total amount of the structural units derived from the monomers constituting the second polymer.

[0111] The solution viscosity of each of the first polymer and the second polymer is preferably 10 to 800 mPa·s, and more preferably 15 to 500 mPa·s, when the polymer is made into a 10% by mass solution. The solution viscosity (mPa·s) is a value measured at 25°C using an E-type rotational viscometer for a 10% by mass polymer solution prepared using a good solvent for the polymer (e.g., γ-butyrolactone, N-methyl-2-pyrrolidone, etc.).

[0112] The polystyrene-equivalent weight average molecular weight (Mw) of each of the first polymer and the second polymer measured by gel permeation chromatography (GPC) is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of Mw to the polystyrene-equivalent number average molecular weight (Mn) measured by GPC, is preferably 7 or less, more preferably 5 or less.

[0113] For example, when the first polymer and the second polymer contained in the liquid crystal alignment agent are polyamic acids, preferred specific embodiments of the combination of the first polymer and the second polymer include the following embodiments [1B] to [3B]. [Aspect 1B] An aspect in which the first polymer is a polyamic acid containing the structural unit (UA), the structural unit (UB) and the structural unit (UC), and the second polymer is a polyamic acid containing the structural unit (UB) but not the structural unit (UA). [Aspect 2B] An aspect in which the first polymer is a polyamic acid containing the structural unit (UA), the structural unit (UB) and the structural unit (UC), and the second polymer is a polyamic acid not containing the structural unit (UA) or the structural unit (UB). [Aspect 3B] An aspect in which the first polymer is a polyamic acid containing the structural unit (UA), the structural unit (UB) and the structural unit (UC), and the second polymer is a polyamic acid containing the structural unit (UC) but not the structural unit (UA). In these embodiments, it is preferred that structural unit (UB) is a different structural unit from structural unit (UA), and it is preferred that structural unit (UC) is a different structural unit from structural unit (UA).

[0114] The content of the first polymer in the liquid crystal alignment agent is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, relative to 100 parts by mass of the total amount of the first polymer and the second polymer. The content of the first polymer is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 55 parts by mass or less, relative to 100 parts by mass of the total amount of the first polymer and the second polymer. The content of the second polymer is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 45 parts by mass or more, relative to 100 parts by mass of the total amount of the first polymer and the second polymer. The content of the second polymer is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, relative to 100 parts by mass of the total amount of the first polymer and the second polymer. By setting the contents of the first polymer and the second polymer within the above ranges, respectively, it is possible to ensure good tilt-imparting properties, and to obtain a liquid crystal alignment film with excellent impurity resistance while shortening the light irradiation time for consuming the photopolymerizable compound during the production of a PSA type liquid crystal element.

[0115] <Other ingredients> The liquid crystal aligning agent may further contain, in addition to the first polymer and the second polymer, a component (other component) different from the first polymer and the second polymer, if necessary.

[0116] Other polymers The liquid crystal alignment agent of the present disclosure may further contain a polymer (other polymer) different from the first polymer and the second polymer. Examples of the other polymer include a polymer having a main skeleton of polyester, polyurea, cellulose derivative, or polyacetal. The content of the other polymer in the liquid crystal alignment agent is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the total amount of the solid content contained in the liquid crystal alignment agent.

[0117] Crosslinking agent The liquid crystal alignment agent of the present disclosure may further contain a crosslinking agent. Examples of the crosslinking agent include a group having a polymerizable carbon-carbon bond, a cyclic ether group, a cyclic thioether group, an isocyanate group, a protected isocyanate group, a methylol group, a protected methylol group, a hydroxyalkylamide group, a protected hydroxyalkylamide group, a cyclic carbonate group, a group "-CR 90 =CR 91 -R 92 -" (but R 90 R is a monovalent organic group that is eliminated by reaction with an amino group. 91 is a hydrogen atom or an alkyl group, R 92 is an electron-withdrawing group.) and compounds having at least one crosslinkable group selected from the group consisting of a silanol group, an amino group, a protected amino group, and an alkoxysilyl group.

[0118] Among the above crosslinkable groups, examples of groups having a polymerizable carbon-carbon bond include a (meth)acryloyl group, a maleimide group, an alkenyl group, a vinylphenyl group, a vinyl ether group, and a 3-methylenetetrahydrofuran-2(3H)-one-5-yl group.

[0119] From the viewpoint of impurity resistance (particularly, reduction of DC afterimage), the crosslinking agent can preferably be a compound having a functional group capable of reacting with an amino group or a carboxy group among the above. Among them, a compound having a total of two or more of at least one selected from the group consisting of a cyclic ether group, a hydroxyalkylamide group, a protected hydroxyalkylamide group, a methylol group, a protected methylol group, a protected isocyanate group, an amino group, a protected amino group, and an alkoxysilyl group in one molecule can be preferably used.

[0120] From the viewpoint of improving the liquid crystal alignment property, electrical properties, and sealant adhesion of a liquid crystal element in a well-balanced manner, the number of crosslinkable groups that the crosslinking agent has in one molecule is preferably 2 to 12, and more preferably 2 to 8. From the viewpoint of ensuring good storage stability, the molecular weight of the crosslinking agent is preferably 1,200 or less, more preferably 1,000 or less, and even more preferably 800 or less.

[0121] Specific examples of the crosslinking agent include compounds having a cyclic ether group, such as N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenyl ether, N,N-diglycidyl-aminomethylcyclohexane, N,N-diglycidyl-cyclohexylamine, cyclic siloxanes having two or more glycidyl groups, and epoxidation products of pentaerythritol tetraallyl ether with hydrogen peroxide; As the compound having a hydroxyalkylamide group or a protected hydroxyalkylamide group, compounds represented by the following formulae (c-1) to (c-3) and the like are included: As the compound having a methylol group or a protected methylol group, the compounds represented by the following formulae (c-4) to (c-9) and the like are mentioned: As the compound having a protected isocyanate group, the compounds represented by the following formulae (c-10) to (c-14) and the like are used: Examples of the compound having an amino group or a protected amino group include the compounds represented by the following formulas (c-15) to (c-19), respectively. [ka] [ka] (In formula (c-8), Ac is an acetyl group.) [ka] (In formula (c-10) and formula (c-11), R 93 is a tert-butoxy group.) [ka]

[0122] When a crosslinking agent is blended into the liquid crystal alignment agent of the present disclosure, the content of the crosslinking agent in the liquid crystal alignment agent is preferably 0.5 parts by mass or more relative to 100 parts by mass of the total amount of the polymer components contained in the liquid crystal alignment agent (i.e., the total amount of the first polymer, the second polymer, and other polymers) from the viewpoint of improving the balance between the liquid crystal alignment property and electrical properties of the liquid crystal element and the sealant adhesion of the liquid crystal alignment film. The content ratio of the crosslinking agent is more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the total amount of the polymer components. In addition, the content of the crosslinking agent is preferably 30 parts by mass or less, and more preferably 20 parts by mass or less, relative to 100 parts by mass of the total amount of the polymer components.

[0123] ·solvent The liquid crystal aligning agent of the present disclosure is prepared as a liquid composition in which the first polymer, the second polymer, and other components used as necessary are preferably dispersed or dissolved in a suitable solvent.

[0124] As the solvent, an organic solvent is preferably used.Specific examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, 1,3-dimethyl-2-imidazolidinone, phenol, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, diacetone alcohol, 1-hexanol, 2-hexanol, propane-1,2-diol, 3-methoxy-1-butanol, ethylene glycol monomethyl ether, methyl lactate, ethyl lactate, butyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl acetoacetate, ethyl acetoacetate, ethyl propionate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, and ethylene glycol-i-propyl ether. Examples of the solvent include ethylene glycol-n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, propylene carbonate, propylene glycol monomethyl ether (PGME), diethylene glycol diethyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol diacetate, cyclopentanone, cyclohexanone, etc. As the solvent, one type can be used alone or two or more types can be mixed and used.

[0125] Other components contained in the liquid crystal alignment agent include, in addition to the above, for example, antioxidants, metal chelate compounds, curing accelerators, surfactants, fillers, dispersants, photosensitizers, etc. The blending ratio of other components can be appropriately selected according to each compound within a range that does not impair the effects of the present disclosure.

[0126] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass %. If the solid content concentration is 1 mass % or more, it is preferable in that the thickness of the coating film can be sufficiently ensured and a liquid crystal alignment film showing better liquid crystal alignment properties can be obtained. On the other hand, if the solid content concentration is 10 mass % or less, the coating film can be made to an appropriate thickness, and a liquid crystal alignment film showing good liquid crystal alignment properties tends to be easily obtained. In addition, the viscosity of the liquid crystal alignment agent becomes appropriate, and the coating property tends to be good.

[0127] <Second Liquid Crystal Alignment Agent> The second liquid crystal alignment agent of the present disclosure contains the above-mentioned first polymer and crosslinking agent. The above description of the first liquid crystal alignment agent applies to details of the type and content of the first polymer and crosslinking agent. The second liquid crystal alignment agent may further contain components such as the above-mentioned solvent in addition to the first polymer and crosslinking agent. The second liquid crystal alignment agent is the same as the first liquid crystal alignment agent except that it does not contain the above-mentioned second polymer.

[0128] <Liquid crystal alignment film and liquid crystal element> The liquid crystal alignment film of the present disclosure is formed by the liquid crystal alignment agent prepared as described above. The liquid crystal element of the present disclosure includes a liquid crystal alignment film formed by using the liquid crystal alignment agent described above. The operation mode of the liquid crystal in the liquid crystal element is not particularly limited, and can be applied to various modes such as TN (Twisted Nematic) type, STN (Super Twisted Nematic) type, VA (Vertical Alignment) type (including VA-MVA type, VA-PVA type, etc.), IPS (In-Plane Switching) type, FFS (Fringe Field Switching) type, OCB (Optically Compensated Bend) type, and PSA (Polymer Sustained Alignment) type. The liquid crystal element can be manufactured by a method including, for example, the following steps 1 to 3. In step 1, the substrate used differs depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.

[0129] (Step 1: Formation of coating film) First, a liquid crystal alignment agent is applied onto a substrate, and the applied surface is preferably heated to form a coating film on the substrate. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass, or plastic such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, or poly(alicyclic olefin) can be used. The transparent conductive film provided on one side of the substrate may be a NESA film (registered trademark of PPG, USA) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), or the like. When manufacturing a TN-type, STN-type, VA-type, or PSA-type liquid crystal element, two substrates each having a patterned transparent conductive film are used. On the other hand, when manufacturing an IPS-type or FFS-type liquid crystal element, a substrate having an electrode made of a transparent conductive film or metal film patterned into a comb shape and an opposing substrate having no electrode are used. The metal film may be, for example, a film made of a metal such as chromium. The liquid crystal alignment agent is preferably applied to the substrate on the electrode-forming surface by offset printing, spin coating, roll coating, or inkjet printing.

[0130] After the liquid crystal alignment agent is applied, preheating (prebaking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent. The prebaking temperature is preferably 30 to 200°C, and the prebaking time is preferably 0.25 to 10 minutes. Thereafter, if necessary, a baking (postbaking) step is performed for the purpose of completely removing the solvent or thermally imidizing the amic acid structure present in the polymer. The baking temperature (postbaking temperature) at this time is preferably 80 to 300°C, and the postbaking time is preferably 5 to 200 minutes. The film thickness of the film thus formed is preferably 0.001 to 1 μm. After the liquid crystal alignment agent is applied on the substrate, the organic solvent is removed to form a liquid crystal alignment film or a coating film that will become a liquid crystal alignment film.

[0131] (Step 2: Orientation Treatment) When a TN-type, STN-type, IPS-type or FFS-type liquid crystal element is manufactured, a treatment (alignment treatment) is carried out to impart liquid crystal alignment ability to the coating film formed in step 1. This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. Examples of the alignment treatment include a rubbing treatment in which the surface of the coating film formed on the substrate is rubbed with cotton or the like, and a photo-alignment treatment in which the coating film is irradiated with light to impart liquid crystal alignment ability. On the other hand, when a vertical alignment type (VA type) liquid crystal element is manufactured, the coating film formed in step 1 can be used as it is as a liquid crystal alignment film, but the coating film may be subjected to an alignment treatment. The liquid crystal alignment film suitable for a vertical alignment type liquid crystal element can also be preferably used for a PSA type liquid crystal element. When a PSA type liquid crystal element is manufactured, a pretilt angle may be imparted by a rubbing treatment.

[0132] The light irradiation in the photo-alignment treatment can be performed by a method of irradiating the coating film after the post-bake step, a method of irradiating the coating film after the pre-bake step but before the post-bake step, or a method of irradiating the coating film during heating in at least one of the pre-bake step and the post-bake step. In the photo-alignment treatment, the radiation to be irradiated to the coating film can be, for example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm. Preferably, ultraviolet light containing light with a wavelength of 200 to 400 nm. When the radiation is polarized, it may be linearly polarized or partially polarized. In addition, when the radiation used is linearly polarized or partially polarized, the radiation may be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When non-polarized radiation is irradiated, the direction of irradiation is an oblique direction.

[0133] The light source used may be, for example, a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, or a meta Examples of the radiation that can be used include an argon resonance lamp, a xenon lamp, and an excimer laser. The radiation dose is preferably 400 to 20,000 J / m 2 and more preferably 1,000 to 5,000 J / m 2The coating film may be irradiated with light while being heated in order to enhance the reactivity.

[0134] In producing a liquid crystal alignment film, the coating film that has been subjected to light irradiation treatment may be heated within a temperature range of 120°C to 280°C to further improve the liquid crystal alignment (thermal realignment). This heating may be post-baking, or may be a heat treatment that is performed after the post-baking separately from the post-baking. In the heat treatment of the coating film that has been subjected to light irradiation treatment, the heating temperature is preferably 140°C or higher, more preferably 150°C to 250°C, from the viewpoint of promoting the realignment of molecular chains by heating. The heating time is preferably 5 to 200 minutes, more preferably 10 to 60 minutes.

[0135] The production of the liquid crystal alignment film may further include a step of contacting the coating film that has been subjected to the light irradiation treatment with water, a water-soluble organic solvent, or a mixed solvent of water and a water-soluble organic solvent. Examples of the water-soluble organic solvent include methanol, ethanol, 1-propanol, isopropanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone. Of these, the solvent used in this step is preferably water, isopropanol, or a mixture thereof. Examples of the method of contacting the coating film with the solvent include, but are not limited to, a spraying (spray) treatment, a shower treatment, a dipping treatment, and a puddle treatment. The contact time between the coating film and the solvent is not particularly limited, but is, for example, 5 seconds to 15 minutes. After contact with the solvent, the coating film may be subjected to a heat treatment.

[0136] (Step 3: Construction of liquid crystal cell) Two substrates on which the liquid crystal alignment film is formed are prepared as described above, and a liquid crystal is placed between the two substrates arranged opposite to each other to manufacture a liquid crystal cell. For example, the liquid crystal cell can be manufactured by (1) arranging two substrates opposite to each other with a gap (spacer) between them so that the liquid crystal alignment films face each other, bonding the peripheries of the two substrates with a sealant, injecting liquid crystal into the substrate surfaces and the cell gap partitioned by the sealant, and then sealing the injection hole; (2) applying a sealant to a predetermined location on one substrate on which the liquid crystal alignment film is formed, dropping liquid crystal at a few predetermined locations on the liquid crystal alignment film surface, bonding the other substrate so that the liquid crystal alignment film faces each other, and spreading the liquid crystal over the entire surface of the substrate (ODF method); and the like. It is desirable to further heat the manufactured liquid crystal cell to a temperature at which the liquid crystal used has an isotropic phase, and then slowly cool it to room temperature to remove the flow orientation during liquid crystal filling.

[0137] As the sealing material, for example, an epoxy resin containing a hardener and aluminum oxide spheres as a spacer can be used. As the spacer, a photo spacer, a bead spacer, etc. can be used. As the liquid crystal, nematic liquid crystal and smectic liquid crystal can be mentioned. Among these, nematic liquid crystal is preferable, and for example, Schiff base liquid crystal, azoxy liquid crystal, biphenyl liquid crystal, phenylcyclohexane liquid crystal, ester liquid crystal, terphenyl liquid crystal, biphenylcyclohexane liquid crystal, pyrimidine liquid crystal, dioxane liquid crystal, bicyclooctane liquid crystal, cubane liquid crystal, etc. can be used. In addition, cholesteric liquid crystal, chiral agent, ferroelectric liquid crystal, etc. may be added to these liquid crystals.

[0138] When manufacturing a PSA type liquid crystal element, first, a liquid crystal cell is constructed by filling a cell gap with a photopolymerizable compound together with liquid crystal. After constructing the liquid crystal cell, a process of irradiating the liquid crystal cell with light is performed with a voltage applied between the conductive films of a pair of substrates in order to impart a pretilt angle to the liquid crystal alignment film. Then, in order to consume the photopolymerizable compound remaining in the liquid crystal, the liquid crystal cell is irradiated for a long time with light that is equal to or weaker than the light irradiation intended to impart a pretilt angle in a state in which no voltage is applied to the liquid crystal cell. Specifically, it is preferable to manufacture a liquid crystal element by a method including the following steps. [1] A step of forming a coating film using a liquid crystal alignment agent on each of the conductive films of a pair of substrates having a conductive film (corresponding to step 1 above) [2] A step of constructing a liquid crystal cell by disposing a pair of substrates on which a coating film has been formed so that the coating films face each other via a liquid crystal layer containing a photopolymerizable compound (corresponding to step 3 above). [3] A step of irradiating the liquid crystal cell with light while a voltage is applied between the conductive films (first irradiation step). [4] After the first irradiation step, a step of irradiating the liquid crystal cell with light having an intensity equal to or weaker than that of the light irradiation in the first irradiation step for a longer period of time than in the first irradiation step and without applying a voltage between the conductive films (second irradiation step).

[0139] As the photopolymerizable compound, a polyfunctional compound having two or more radically polymerizable functional groups such as an acryloyl group, a (meth)acryloyl group, a vinyl group, etc. can be preferably used. From the viewpoint of reactivity, the photopolymerizable compound is preferably a polyfunctional (meth)acrylic compound having two or more (meth)acryloyl groups. In addition, from the viewpoint of stably maintaining the alignment of liquid crystal molecules, a compound having a total of two or more rings of at least one of a cyclohexane ring and a benzene ring as a liquid crystal skeleton can be preferably used as the photopolymerizable compound. Note that, as such a photopolymerizable compound, a conventionally known compound can be used. In manufacturing a PSA type liquid crystal element, the proportion of the photopolymerizable compound used is, for example, 0.01 to 3 parts by mass, preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the liquid crystal in total.

[0140] The voltage applied to the liquid crystal cell in the first irradiation step can be, for example, 5 to 50 V DC or AC. As the light to be irradiated, for example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used, and ultraviolet light containing light with a wavelength of 300 to 400 nm is preferred. As the light source for the irradiation light, for example, a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. The light irradiation dose is preferably 1,000 J / m 2 More than 200,000J / m 2 or less, more preferably 1,000 to 100,000 J / m 2 The intensity of the light irradiated onto the liquid crystal cell in the first irradiation step is preferably 0.1 to 400 mW / cm. 2 The light irradiation time in the first irradiation step (also referred to as "UV 1 hour") is preferably 10 to 200 seconds.

[0141] In the second irradiation step, the liquid crystal cell after being irradiated with light in the first irradiation step is irradiated with light without applying a voltage. The light irradiated to the liquid crystal cell in the second irradiation step and the light source of the irradiated light are the same as those described in the first irradiation step. The intensity of the light irradiated to the liquid crystal cell in the second irradiation step is preferably 0.1 to 200 mW / cm. 2 and more preferably 0.1 to 100 mW / cm 2 and more preferably 0.1 to 30 mW / cm 2 and even more preferably 0.1 to 5.0 mW / cm 2 The light irradiation time in the second irradiation step (also referred to as "UV 2 hours") is longer than UV 1 hour, and is preferably 45 to 200 minutes. The light irradiation dose (J / m 2 ) may be the same as the light irradiation in the first irradiation step, or may be more or less than the light irradiation in the first irradiation step. In addition, for example, when some or all of the light irradiation conditions in the first irradiation step and the second irradiation step are the same, the first irradiation step and the second irradiation step may be performed consecutively.

[0142] In particular, when a PSA type liquid crystal cell is manufactured using the liquid crystal alignment agent of the present disclosure, the UV2 time can be shortened, which can minimize damage to the liquid crystal cell caused by light irradiation and shorten the manufacturing time.

[0143] Next, a polarizing plate is attached to the outer surface of the liquid crystal cell as needed. Examples of polarizing plates include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, or a polarizing plate made of the H film itself. This produces a liquid crystal element.

[0144] The liquid crystal element of the present disclosure can be effectively applied to various applications, specifically, for example, it can be used as various display devices such as clocks, portable game machines, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as light control devices, retardation films, and the like.

[0145] According to the present disclosure, the following means are provided. [Measure 1] “*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and includes a structural unit derived from a diamine having "*-X 1 -W 1 " at its side chain, and a second polymer which is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane, and addition polymer, and which is substantially free of a structural unit having a benzophenone structure, wherein the at least one selected from the group consisting of the first polymer and the second polymer has a secondary amino group, a tertiary amino group, 1 -NR 1 -* 2and nitrogen-containing heterocyclic structures (wherein R 1 is a monovalent leaving group. 1 " and "* 2 " represents a bond to a carbon atom other than the carbon in the (thio)carbonyl group. A liquid crystal aligning agent comprising a structural unit derived from a diamine having the formula: [Means 2] The liquid crystal aligning agent according to [Means 1], wherein the first polymer is at least one selected from the group consisting of polyamic acid and polyimide. [Means 3] The liquid crystal aligning agent according to [Means 1] or [Means 2], wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit derived from the diamine having the nitrogen-containing heterocyclic structure. [Means 4] The liquid crystal aligning agent according to any one of [Means 1] to [Means 3], wherein the first polymer is a polyamic acid. [Means 5] The liquid crystal aligning agent according to any one of [Means 1] to [Means 4], wherein the second polymer is at least one selected from the group consisting of polyamic acid and polyimide, contains a structural unit derived from a tetracarboxylic acid anhydride, and a ratio of a structural unit derived from an aromatic tetracarboxylic acid dianhydride among the structural units derived from the tetracarboxylic acid anhydride is 50 mol % or less. [Means 6] The liquid crystal aligning agent according to any one of [Means 1] to [Means 5], wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit having a vertical alignment group. [Means 7] At least one selected from the group consisting of the first polymer and the second polymer has a *-NR 2 -CO- or *-CO-NR 2 - is bonded to the partial structure (where R 2 is a hydrogen atom or a monovalent organic group. "*" represents a bond to an aromatic ring. The liquid crystal aligning agent according to any one of [Means 1] to [Means 6], comprising a structural unit derived from a diamine having [Means 8] The liquid crystal aligning agent according to any one of [Means 1] to [Means 7], further comprising a crosslinking agent. [Means 9] “*-X1 -W 1 The liquid crystal aligning agent according to any one of [Means 1] to [Means 8], wherein the diamine having a group represented by the formula (CA-1) is represented by the above formula (CA-1). [Means 10] “*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and includes a structural unit derived from a diamine having "*-X 1 -W 1 A liquid crystal aligning agent comprising: a polymer having a group represented by the formula: [Measure 11] A liquid crystal alignment film formed by using the liquid crystal aligning agent according to any one of [Measure 1] to [Measure 10]. [Means 12] A liquid crystal element comprising the liquid crystal alignment film of [Means 11]. [Means 13] A compound represented by the above formula (CA-1-1). EXAMPLES

[0146] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0147] In the following examples, the imidization rate of polyimide and the molecular weights (Mw, Mn) of the polymer were measured by the following methods. <Imidization rate of polyimide> The polyimide solution was poured into pure water, and the resulting precipitate was thoroughly dried under reduced pressure at room temperature. It was then dissolved in deuterated dimethyl sulfoxide and measured at room temperature using tetramethylsilane as a standard substance. 1 H-NMR measurement was performed. 1 The imidization rate [%] was calculated from the H-NMR spectrum using the following formula (1). Imidization rate [%] = (1-(β 1 / (β 2 ×α)))×100 …(1) (In formula (1), β 1 is the peak area due to the proton of the NH group that appears at a chemical shift of around 10 ppm, and β 2is the peak area due to other protons, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid). <Molecular weight of polymer (Mw, Mn)> The weight average molecular weight (Mw) and number average molecular weight (Mn) were measured by gel permeation chromatography (GPC) under the following conditions. Equipment: Showa Denko Co., Ltd. "GPC-101" GPC column: Shimadzu GLC's "GPC-KF-801", "GPC-KF-802", "GPC-KF-803" and "GPC-KF-804" combined Mobile phase: Tetrahydrofuran (THF) Column temperature: 40℃ Flow rate: 1.0mL / min Sample concentration: 1.0% by mass Sample injection volume: 100 μL Detector: Differential refractometer Standard material: Monodisperse polystyrene

[0148] The abbreviations of the compounds used in the following examples are shown below. For convenience, hereinafter, a "compound represented by formula (X)" may be simply referred to as "compound (X)".

[0149] (Tetracarboxylic dianhydride) TA-1~TA-8 [ka]

[0150] (Diamine)DA-1~DA-10, daa-1~daa-3 [ka] [ka]

[0151] (Diamine) DB-1~DB-12 [ka]

[0152] (Diamine) DC-1 to DC-17 [ka]

[0153] (Other monomers, carboxylic acids) M-1 to M-9, S-1, C-1 [ka]

[0154] (Additives) AD-1 to AD-10 [ka]

[0155] <Synthesis of Monomer> [Synthesis Example 1A] Compound (DA-3) was synthesized according to the following scheme. [ka]

[0156] 3.85 mmol of 4-hydroxybenzophenone, 4.62 mmol of 3,5-dinitrobenzyl chloride, 4.62 mmol of potassium carbonate, and 8 mL of N,N-dimethylformamide (DMF) were added to a 50 mL eggplant flask. The reaction temperature was raised from room temperature to 80°C and stirred for 1 hour. After confirming the completion of the reaction by LC-MS analysis, the mixture was cooled to room temperature. Then, ethyl acetate and water were added for liquid separation and purification, and the organic layer was concentrated. The obtained purple solid was dried to obtain 1.45 g of compound (DA-3-1) (yield: 99%). Next, 3.83 mmol of compound (DA-3-1), 76.7 mmol of zinc powder, 38.3 mmol of ammonium chloride, 8.7 mL of tetrahydrofuran (THF), and 1.5 mL of ethanol (EtOH) were added to a 50 mL eggplant flask, and then cooled to 0°C in an ice bath. While stirring the reaction solution, 109 mmol of distilled water was added dropwise. After continuing stirring at 0°C for 10 minutes, the reaction temperature was raised to room temperature and stirred for an additional 4 hours. After confirming the completion of the reaction by LC-MS analysis, zinc was removed by celite filtration. Ethyl acetate and water were added to the filtrate for separation and purification, and the organic layer was concentrated. The obtained solid was dried to obtain 1.16 g of the desired diamine (DA-3) (yield 95%, ocher solid). The structure of diamine (DA-3) was 1 The diamine (DA-3) was confirmed by H-NMR spectrum. 1 The H-NMR spectrum is shown in Figure 1.

[0157] <Polymer synthesis> 1. Synthesis of polyamic acid [Synthesis Example 1] 15 molar parts of compound (TA-1) and 85 molar parts of compound (TA-3) as tetracarboxylic dianhydrides, and 30 molar parts of compound (daa-1), 30 molar parts of compound (DB-12), 30 molar parts of compound (DC-14), and 10 molar parts of compound (DC-2) as diamine compounds were dissolved in N-methyl-2-pyrrolidone (NMP) and reacted at 60° C. for 6 hours to obtain a solution containing 20 mass% of polyamic acid (referred to as polymer (PAA-1)).

[0158] [Synthesis Examples 2-20] Polyamic acids (polymers (PAA-2) to (PAA-20)) were obtained by the same procedure as in Synthesis Example 1, except that the types and amounts of the tetracarboxylic dianhydrides and diamine compounds used were changed as shown in Table 1. In Table 1, the values ​​of the tetracarboxylic dianhydrides (acid dianhydrides 1 to 3) represent the ratio (molar ratio) of each compound to 100 parts by mole of the total amount of the tetracarboxylic dianhydrides used in the synthesis of the polymers. The values ​​of the diamine compounds (diamines 1 to 5) represent the ratio (molar ratio) of each compound to 100 parts by mole of the total amount of the diamine compounds used in the synthesis of the polymers.

[0159] 2. Synthesis of Polyimide [Synthesis Example 21] As tetracarboxylic dianhydrides, 90 mol parts of compound (TA-1) and 10 mol parts of compound (TA-6), and as diamine compounds, 10 mol parts of compound (DA-6), 20 mol parts of compound (DB-8), 20 mol parts of compound (DC-14), 30 mol parts of compound (DC-5) and 20 mol parts of compound (DC-13) were dissolved in NMP and reacted at 60 ° C for 6 hours to obtain a solution containing 20 mass% of polyamic acid. Next, NMP was added to the obtained polyamic acid solution to obtain a solution with a polyamic acid concentration of 10 mass%, and pyridine and acetic anhydride were added to perform a dehydration ring-closing reaction at 80 ° C for 4 hours. After the dehydration ring-closing reaction, the solvent in the system was replaced with new NMP to obtain a solution containing 15 mass% of polyimide (this is polymer (PI-1)) with an imidization rate of about 70%.

[0160] [Synthesis Example 22] A polyimide (polymer (PI-2)) was obtained in the same manner as in Synthesis Example 21, except that the types and amounts of the tetracarboxylic dianhydride and diamine compound used were changed as shown in Table 1.

[0161] [Table 1]

[0162] 3.Synthesis of styrene-maleimide copolymer [Synthesis Example 23] Under nitrogen, 40 mol parts of compound (M-2), 40 mol parts of compound (M-3) and 20 mol parts of compound (M-8) were added to a 100 mL two-neck flask relative to a total of 100 mol parts of polymerization monomers, 0.3922 g of 2,2'-azobis(2,4-dimethylvaleronitrile) as a radical polymerization initiator (10 parts by mass relative to 100 parts by mass of the total amount of polymerization monomers), and 15.68 g of N-methyl-2-pyrrolidone (NMP) as a solvent (400 parts by mass relative to 100 parts by mass of the total amount of polymerization monomers) were added, and polymerization was carried out for 6 hours at 70 ° C. After reprecipitation in methanol, the precipitate was filtered and dried in vacuum at room temperature for 8 hours to obtain the desired addition polymer (this is referred to as polymer (PM-1)).

[0163] [Synthesis Example 24] An addition polymer (referred to as polymer (PM-2)) was obtained in the same manner as in Synthesis Example 23, except that the types and amounts of the polymerization monomers used were changed as shown in Table 2.

[0164] [Table 2]

[0165] 4. Synthesis of polyorganosiloxane [Synthesis Example 25] In a 1000mL three-neck flask, 100.0g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (compound (S-1)), 500g of methyl isobutyl ketone, and 10.0g of triethylamine were charged and mixed at room temperature. Next, 100g of deionized water was dropped from the dropping funnel over 30 minutes, and then the reaction was carried out at 80°C for 6 hours while mixing under reflux. After the reaction was completed, the organic layer was taken out and washed with a 0.2% by mass aqueous solution of ammonium nitrate until the water after washing became neutral, and then the solvent and water were distilled off under reduced pressure. An appropriate amount of methyl isobutyl ketone was added to obtain a 50% by mass solution of polyorganosiloxane having an epoxy group (referred to as "polymer (PS-1)").

[0166] [Synthesis Example 26] Polymer (PS-1) was obtained in the same manner as in Synthesis Example 25. Compound (C-1) was added to a 500 mL three-neck flask at 20 mol% relative to the amount of epoxy groups in polymer (PS-1), 1.00 g of tetrabutylammonium bromide, 20.0 g of a solution containing polymer (PS-1), and 290.0 g of methyl isobutyl ketone, and the mixture was stirred at 90 ° C. for 18 hours. After cooling to room temperature, the mixture was subjected to separation and washing with distilled water 10 times. Thereafter, the organic layer was collected, concentrated by a rotary evaporator and diluted with NMP twice, and then adjusted to a solid content concentration of 10 mass% using NMP to obtain an NMP solution of polyorganosiloxane (this is referred to as polymer (PS-2)).

[0167] [Table 3]

[0168] <Preparation and Evaluation of Liquid Crystal Alignment Agent> [Example 1] 1. Preparation of Liquid Crystal Alignment Agent A solution containing 50 parts by mass of the polymer (PAA-11) obtained in Synthesis Example 11 and a solution containing 50 parts by mass of the polymer (PAA-6) obtained in Synthesis Example 6 were mixed and further diluted with N-methyl-2-pyrrolidone (NMP), gamma butyrolactone (GBL), butyl cellosolve (BC), diacetone alcohol (DAA) and diethylene glycol diethyl ether (DEDG) to obtain a solution with a solvent composition of NMP / GBL / BC / DAA / DEDG=30 / 30 / 15 / 15 / 10 (mass ratio) and a solid content concentration of 3.5 mass%. The liquid crystal alignment agent (AL-1) was prepared by filtering this solution through a filter with a pore size of 0.2 μm.

[0169] 2. Preparation of Liquid Crystal Composition 5% by mass of a liquid crystal compound represented by the following formula (L1-1) and 0.3% by mass of a photopolymerizable compound represented by the following formula (L2-1) were added to 10 g of nematic liquid crystal (MLC-6608, manufactured by Merck) and mixed to obtain liquid crystal composition LC1. [ka]

[0170] 3. Preparation of insulating film forming composition In a flask equipped with a cooling tube and a stirrer, 7 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile), 200 parts by mass of propylene glycol monomethyl ether acetate, 15 parts by mass of methacrylic acid, 30 parts by mass of glycidyl methacrylate, 20 parts by mass of styrene, 5 parts by mass of 2-hydroxyethyl acrylate, and 30 parts by mass of isobornyl acrylate were charged, and after nitrogen replacement, gentle stirring was started. After the reaction solution was raised to 62°C, this temperature was maintained for 5 hours to obtain a polymer solution containing an acrylic copolymer (R-1). The obtained polymer solution was dropped into 900 parts by mass of hexane to precipitate the acrylic copolymer (R-1). The precipitated acrylic copolymer (R-1) was separated, and 150 parts by mass of propylene glycol monomethyl ethyl acetate was added, heated to 40°C, and distilled under reduced pressure to obtain a polymer solution containing an acrylic copolymer (R-1). The solid concentration of the obtained polymer solution containing the acrylic copolymer (R-1) was 30 mass %, and as a result of GPC analysis, the area of ​​unreacted monomer and polymerization initiator was 2.3%, and the weight average molecular weight (Mw) was 12,800. For an amount equivalent to 100 parts by mass (solid content) of the acrylic copolymer (R-1), 25 parts by mass of a condensation product of 4,4'-[1-[4-[1-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonic acid chloride (2.0 mol) were used as a photosensitizer, and a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate ("KAYARAD" manufactured by Nippon Kayaku Co., Ltd.) was used as a polymerizable compound. A mixture of 5 parts by mass of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Kyowa Hakko Kirin's "Kyowanol M") as a film-forming aid, 10 parts by mass of SH28PA (Dow Corning Toray) as a leveling agent, and diethylene glycol ethyl methyl ether was added to the mixture to give a solids concentration of 18% by mass. The mixture was then filtered through a membrane filter having a pore size of 0.2 μm to prepare a composition for forming an insulating film (RD-1).

[0171] 4. Fabrication of PSA-type liquid crystal cells for evaluation The liquid crystal alignment agent (AL-1) prepared above was applied using a spinner onto the transparent electrode surface of a glass substrate with a transparent electrode made of an ITO film, and pre-baked on a hot plate at 80°C for 1 minute. The substrate was then heated at 200°C for 1 hour in an oven substituted with nitrogen to remove the solvent, forming a coating film (liquid crystal alignment film) with a thickness of 0.08 μm, and a pair (2 sheets) of substrates with liquid crystal alignment films were obtained. An epoxy resin adhesive containing aluminum oxide spheres with a diameter of 3.5 μm was applied by screen printing to the outer periphery of the surface having the liquid crystal alignment film of one of the above substrates, and then the liquid crystal alignment film surfaces of the pair of substrates were placed opposite each other, overlapped and pressed together, and the adhesive was thermally cured by heating at 150° C. for 1 hour. Next, liquid crystal composition LC1 was filled into the gap between the substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive. In order to eliminate flow alignment during liquid crystal injection, the resultant was heated at 150° C. for 10 minutes and then slowly cooled to room temperature. Next, an AC voltage of 10 V with a frequency of 60 Hz was applied between the electrodes of the obtained liquid crystal cell, and while the liquid crystal was in a driven state, an ultraviolet ray irradiation device using a metal halide lamp as a light source was used to irradiate the liquid crystal with an intensity of 50,000 J / m2 The liquid crystal cell was irradiated with ultraviolet light at an intensity of 3.22 mW / cm using the same ultraviolet light irradiation device as in the first irradiation, without applying a voltage between the electrodes. 2 The substrate was irradiated with ultraviolet light for 100 minutes (=UV 2 hours) (second irradiation). The first irradiation was for imparting a tilt angle to the liquid crystal near the organic film formed by the liquid crystal alignment agent, and the second irradiation was for the purpose of consuming the photopolymerizable compound remaining in the liquid crystal. In this way, a PSA type liquid crystal cell was manufactured.

[0172] 5. Evaluation of tilt imparting ability Using the PSA type liquid crystal cell for evaluation manufactured in 4. above, the tilt angle value of the liquid crystal molecules from the substrate surface was measured by a crystal rotation method using He-Ne laser light in accordance with the method described in the non-patent documents "TJ Scheffer et.al., J.Appl.Phys. vol.48, p.1783(1977)" and "F.Nakano,et.al., JPN.J.Appl.Phys. vol.19, p.2013(1980)", and this was taken as the pretilt angle. When the pretilt angle of the PSA type liquid crystal cell for evaluation was less than 88.5°, it was judged as "good (○)", when it was 88.5° or more and less than 89.0°, it was judged as "fair (△)", and when it was 89.0° or more, it was judged as "poor (×)". As a result, the tilt imparting property of this example was "good (○)".

[0173] 6. Evaluation of light exposure time (UV 2 hours) in the second exposure A PSA type liquid crystal cell for evaluation was manufactured in the same manner as in 4. above, except that the ultraviolet irradiation time (UV2 hours) in the second irradiation was changed from 100 minutes to 50 minutes. For this PSA liquid crystal cell for evaluation, the tilt angle value of the liquid crystal molecules from the substrate surface was measured by the rotational crystal method using He-Ne laser light in the same manner as in "5. Evaluation of tilt imparting property", and this was taken as the pretilt angle. The pretilt angle before applying a voltage to the liquid crystal cell (this is referred to as the "initial pretilt angle θini") and the pretilt angle after driving for 48 hours at room temperature on a backlight at AC9V (this is referred to as the "pretilt angle after driving θac") were measured. In addition, the pretilt angle change rate β [%] was calculated by the following formula (y) using the measured initial pretilt angle θini and pretilt angle after driving θac. β[%]=[(θac-θini / θini]×100 ···(y) The UV2 time is the light irradiation time required to consume the photopolymerizable compound in the liquid crystal layer, and if the desired pretilt angle can be imparted even when this time is shortened, the UV2 time can be shortened in that liquid crystal cell, and it can be said to be good. When the pretilt angle change rate β was less than 3%, it was evaluated as "good (○)", when it was 3% or more and less than 5%, it was evaluated as "fair (△)", and when it was 5% or more, it was evaluated as "poor (×)". As a result, the UV2 time of this example was evaluated as "good (○)".

[0174] 7. Evaluation of sealing material adhesion A liquid crystal alignment agent (AL-1) was applied onto a glass substrate using a spinner, prebaked on a hot plate at 80°C for 2 minutes, and then heated (post-baked) for 30 minutes in an oven at 230°C with the interior replaced with nitrogen, forming a coating film (liquid crystal alignment film) with an average thickness of 0.10 μm. By repeating the same operation, two glass substrates with coating films were produced. An ODF sealant (S-WB42, manufactured by Sekisui Chemical Co., Ltd.) was applied to the coating film of one of the glass substrates with the coating film formed thereon to a width of 0.5 mm, and the other glass substrate was laminated so that the coating film and the ODF sealant were in contact with each other. After that, a metal halide lamp was used to apply 30,000 J / m 2After irradiating the specimen with light (converted to 365 nm), the specimen was heated in an oven at 120° C. for 1 hour. The adhesion strength was then measured using a compression and tension tester (model number: SDWS-0201-100SL) manufactured by Imada Seisakusho to evaluate the adhesion of the sealant. The evaluation is adhesion strength of 180N / cm 2 If it is more than 150N / cm, it is considered to be "Good (○)". 2 More than 180N / cm 2 If it is less than 150N / cm, it is "Fair (△)". 2 If the adhesion was less than 10%, it was rated as "bad (x)". As a result, the adhesion of the sealing material in this example was rated as "good (◯)".

[0175] 8. Manufacture of liquid crystal cells for evaluating impurity tolerance A glass substrate having an ITO electrode patterned into a comb shape and a glass substrate having no electrode were prepared. An insulating film forming composition (RD-1) was applied to the glass substrate having no electrode by a spin coater, and then prebaked on a hot plate at 90°C for 2 minutes. Next, a proximity exposure machine (Canon's "MA-1200" (ghi line mixed)) was used to expose the glass substrate to 300 mJ / cm2. 2 After irradiating the entire surface of the substrate with light, the substrate was cured by heating (post-baking) at 230° C. for 30 minutes in an oven to form an insulating film with a thickness of 3 μm on the glass substrate. A liquid crystal alignment agent (AL-1) was applied by a spinner to the electrode formation surface of the substrate having an ITO electrode patterned into a comb shape, and to the insulating film formation surface of the substrate having an insulating film, and pre-baked for 1 minute on a hot plate at 80°C. After that, the substrate was heated at 230°C for 1 hour in an oven with the interior replaced with nitrogen, to produce a pair (2 substrates) of substrates having a liquid crystal alignment film with a thickness of 0.1 μm. An epoxy resin adhesive containing aluminum oxide spheres having a diameter of 3.5 μm was applied by screen printing to the outer circumference of the surface having the liquid crystal alignment film of the substrate having an insulating film, and then the liquid crystal alignment film surfaces of a pair of substrates were opposed to each other and pressed together, and the adhesive was thermally cured at 150° C. for 1 hour. Next, the liquid crystal composition LC1 was filled into the gap between the substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive. Furthermore, in order to remove the flow alignment during liquid crystal injection, the liquid crystal cell was heated at 130° C. and then slowly cooled to room temperature to produce a liquid crystal cell for impurity resistance evaluation. Since the substrate can be easily produced, the liquid crystal cell for impurity resistance evaluation was produced using an electrode substrate for an IPS type liquid crystal cell.

[0176] 9. Evaluation of impurity tolerance by VHR The liquid crystal cell for evaluating impurity resistance manufactured in 8 above was placed in an oven at 60°C, and then the voltage holding ratio (VHR) was measured under the conditions of 1V and 1670 milliseconds using a VHR measuring device "VHR-1" manufactured by Toyo Corporation. If the VHR was higher than 60%, it was rated "good (○)", if it was 60% or less and 45% or more, it was rated "passable (△)", and if it was less than 45%, it was rated "poor (×)". As a result, the impurity resistance based on the VHR of this example was rated "good (○)".

[0177] 10. Evaluation of impurity tolerance using residual DC The liquid crystal cell for evaluating impurity resistance manufactured in 8. above was driven at AC2.5V to set the luminance difference between any two pixels to 0, and then DC1V was applied to only one pixel for 20 minutes while driving at AC2.5V to accumulate charge. When the application of DC1V was stopped and the driving was returned to AC2.5V only, a luminance difference occurred between the two pixels due to the accumulated charge. By observing the change in this luminance difference over time, the relaxation time during which the residual DC value decayed was calculated. When the relaxation time was less than 10 seconds, it was judged as "good (○)", when the relaxation time was 10 seconds or more but less than 30 seconds, it was judged as "fair (△)", and when the relaxation time was 30 seconds or more, it was judged as "poor (×)". As a result, the impurity resistance due to residual DC in this example was evaluated as "good (○)".

[0178] [Examples 2 to 14 and Comparative Examples 1 to 7] A liquid crystal alignment agent was prepared in the same manner as in Example 1, except that the types and amounts of the polymer and additives used in the preparation of the liquid crystal alignment agent were changed as shown in Table 4. In addition, a liquid crystal cell for evaluation was produced in the same manner as in Example 1 using the obtained liquid crystal alignment agent, and various evaluations were performed. The evaluation results are shown in Table 4. In Table 4, the numerical values ​​in the polymer column and additive column indicate the blending ratio (parts by mass) of the solid content of each compound relative to 100 parts by mass of the total amount of the polymer components used in the preparation of the liquid crystal alignment agent.

[0179] [Table 4]

[0180] As shown in Table 4, the liquid crystal alignment agents of Examples 1 to 14 were evaluated as good (○) or fair (△) in tilt-imparting property, UV2 hours, sealant adhesion, and impurity resistance, and were well-balanced in various properties. In contrast, Comparative Examples 1 to 4, which did not contain a polymer containing a structural unit derived from a specific diamine (first diamine) having a benzophenone structure, were evaluated as poor (×) in at least one of tilt-imparting property, UV2 hours, sealant adhesion, and impurity resistance, and were inferior to Examples 1 to 14. In addition, Comparative Example 5, which used only a polymer not containing a structural unit having a specific nitrogen-containing structure, was evaluated as poor in impurity resistance. Furthermore, when Comparative Examples 6 and 7, which contained only one type of polymer, were compared with Examples 1 to 14, Comparative Example 6 was evaluated as poor in impurity resistance using VHR as an index, and Comparative Example 7 was evaluated as poor in sealant adhesion.

[0181] From the above results, it is clear that the liquid crystal alignment agent of the present disclosure can provide a liquid crystal alignment film having excellent impurity resistance, tilt imparting property, and sealant adhesion, and can also shorten the light irradiation time for consuming the photopolymerizable compound during the production of a PSA type liquid crystal element.

Claims

1. "*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and a structural unit derived from a diamine having "*-X 1 -W 1 " a first polymer having a group represented by the formula: " at a side chain; a second polymer which is at least one selected from the group consisting of polyamic acid, polyimide, polyorganosiloxane, and addition polymer, and which is substantially free of a structural unit having a benzophenone structure; Contains At least one selected from the group consisting of the first polymer and the second polymer has a secondary amino group, a tertiary amino group, 1 -NR 1 -* 2 and a nitrogen-containing structure selected from the group consisting of nitrogen-containing heterocyclic structures (wherein R 1 is a monovalent leaving group. 1 " and "* 2 " represents a bond to a carbon atom other than the carbon in the (thio)carbonyl group. A liquid crystal aligning agent comprising a structural unit derived from a diamine having the formula:

2. The liquid crystal aligning agent according to claim 1 , wherein the first polymer is at least one selected from the group consisting of polyamic acid and polyimide.

3. The liquid crystal aligning agent according to claim 1 , wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit derived from the diamine having the nitrogen-containing heterocyclic structure.

4. The liquid crystal aligning agent according to claim 1 , wherein the first polymer is a polyamic acid.

5. the second polymer is at least one selected from the group consisting of polyamic acid and polyimide, and contains a structural unit derived from a tetracarboxylic acid anhydride; 2. The liquid crystal aligning agent according to claim 1, wherein the ratio of the structural units derived from the aromatic tetracarboxylic dianhydride to the structural units derived from the tetracarboxylic anhydride is 50 mol % or less.

6. The liquid crystal aligning agent according to claim 1 , wherein at least one selected from the group consisting of the first polymer and the second polymer contains a structural unit having a vertical aligning group.

7. At least one selected from the group consisting of the first polymer and the second polymer has an aromatic ring having *-NR 2 -CO- or *-CO-NR 2 A partial structure in which - is bonded (wherein R 2 is a hydrogen atom or a monovalent organic group. "*" represents a bond to an aromatic ring. The liquid crystal aligning agent according to claim 1, comprising a structural unit derived from a diamine having the following structure:

8. The liquid crystal aligning agent according to claim 1 , further comprising a crosslinking agent.

9. "*-X 1 -W 1 The liquid crystal aligning agent according to claim 1, wherein the diamine having a group represented by the formula (CA-1) is represented by the following formula: 【Chemistry 1】 (In formula (CA-1), X 1 is a divalent linking group. 2 is a single bond or "*-X 1 -W 1 " is a divalent group having a partial structure represented by the formula: 5 and R 6 are each independently a monovalent substituent. r1 is an integer of 0 to 4. r2 is an integer of 0 to 5.

10. "*-X 1 -W 1 " (wherein X 1 is a divalent linking group. 1 is a monovalent group having a benzophenone structure. "*" represents a bond.) and a structural unit derived from a diamine having "*-X 1 -W 1 " a polymer having a group represented by the formula: " at a side chain; A cross-linking agent; A liquid crystal aligning agent comprising:

11. A liquid crystal alignment film formed by using the liquid crystal aligning agent according to any one of claims 1 to 10.

12. A liquid crystal element comprising the liquid crystal alignment film according to claim 11.

13. A compound represented by the following formula (CA-1-1): 【Chemistry 2】 (In formula (CA-1-1), R 8 is an alkanediyl group having 1 to 10 carbon atoms. 1 is an oxygen atom or -NR 9 - is. 9 R is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a monovalent thermally detachable group. 5 and R 6 are each independently a monovalent substituent. r1 is an integer from 0 to 4. r2 is an integer from 0 to 5.

Citation Information

Patent Citations

  • Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

    WO2015033921A1